Ceramic green body, method for manufacturing sintered product, and solvent annealing apparatus

By using carbonate-based polymers and alkali metal-containing ceramic particles, combined with solvent annealing technology, the problem of high flammability in the heating process of ceramic green bodies is solved, and faster processing and high-quality sintered products are achieved.

CN119894848APending Publication Date: 2025-04-25CORNING INC
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202380059992.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-06-02
Filing Date
2023-08-16
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

The existing ceramic green bodies are highly flammable during heating, resulting in a decrease in the quality of sintered products and limited processing rate.

Method used

Carbonate-based polymers are used as binders, combined with alkali metal-containing ceramic particles, and solvent annealing technology is used to control the solvent removal rate, reduce heat flow and increase the processing rate.

Benefits of technology

It realizes faster processing of ceramic green bodies and the formation of high-quality sintered products, reducing the probability of defects during heating.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005272311390000131
    Figure BDA0005272311390000131
  • Figure BDA0005272311390000141
    Figure BDA0005272311390000141
  • Figure BDA0005272311390000291
    Figure BDA0005272311390000291
Patent Text Reader

Abstract

The ceramic green body includes from about 5 wt% to about 20 wt% of a carbonate-based polymer, from about 70 wt% to about 95 wt% of alkali metal-containing ceramic particles, from 0 wt% to about 5 wt% of a dispersant, and from 0 wt% to about 5 wt% of a viscosity modifier. The method includes heating the green ceramic body at about 300 DEG C or less for about 4 minutes or less to remove about 70% by weight or more of the organic material from the green ceramic body. The sintered article includes a relative density that is about 90% or greater of the theoretical density. The ceramic green body comprises a carbonate-based polymer and alkali metal-containing ceramic particles. The solvent annealing equipment comprises a casting chamber, a solvent loading chamber and a drying chamber. The method includes casting the green body in an environment where the vapor pressure of the solvent in the green body is about 1000 Pascals or greater.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] This application claims priority to U.S. Provisional Application No. 63 / 470,598, filed June 2, 2023, and U.S. Provisional Application No. 63 / 400,488, filed August 24, 2022, based on 35 U.S. SC §119, the contents of which are incorporated herein by reference in their entirety. Technical Field

[0002] This disclosure relates to solvent annealing equipment, methods using solvent annealing equipment, ceramic green bodies, sintered products, and methods for manufacturing the same. More specifically, it relates to solvent annealing equipment including a solvent loading chamber, ceramic green bodies containing carbonate-based polymers, sintered products made from ceramic green bodies, and methods for manufacturing the same. Background Technology

[0003] Sintered ceramic products can be used in batteries (e.g., cathodes, solid electrolytes) or as protective covers for consumer electronics devices. It is known to form sintered ceramic products by heating a ceramic green body to remove organic materials followed by sintering. The use of poly(vinyl butyral) to form ceramic green bodies is known. However, the processing of ceramic green bodies containing poly(vinyl butyral) is limited by the heating rate required to produce high-quality sintered products. Therefore, there is a need to develop alternative formulations for ceramic green bodies that can be used to form sintered products at a faster processing rate. Summary of the Invention

[0004] This disclosure provides ceramic green bodies comprising carbonate-based polymers, sintered articles formed from the ceramic green bodies, and methods for manufacturing the same. Providing carbonate-based polymers allows for faster processing of the resulting ceramic green bodies to form sintered articles, for example, by reducing the occurrence of events that could compromise the quality of the sintered articles during the heating of the ceramic green bodies. For example, carbonate-based polymers can provide reduced flammability during the heating of the ceramic green bodies. Flammability is associated with larger molecular weights (e.g., 200 Daltons or greater) corresponding to the bonding of multiple monomers, which can result as a consequence of chain scission during heating. It is not intended to be theoretically limited to the depolymerization of carbonate-based polymers and acrylate-based polymers (e.g., methacrylate-based polymers) in addition to chain scission, while other polymers decompose only through chain scission. However, as demonstrated by the examples below, it was unexpectedly found that in the presence of alkali metal-containing ceramic particles, methacrylate-based polymers decompose primarily through chain scission, while carbonate-based polymers decompose primarily through depolymerization. It is undesirable to be limited by theory that alkali metal-containing ceramic particles will cause debonding problems (i.e., removal of the organic components of the ceramic green body) within a short period of time (e.g., about 4 minutes or less) because alkali metals catalyze the chain scission of flammable components (e.g., polymers) in the binder system, which can damage the ceramic and / or the resulting sintered product. Providing reduced heat flux (e.g., about 7 W / g ceramic green body or less, about 2 W / g polymer in the ceramic green body) can reduce the probability of introducing defects during heating, such as flammability from runaway thermal decomposition or polymer decomposition, and / or enable faster processing of ceramic green bodies while maintaining high-quality sintered products.

[0005] Heating the alkali metal-containing ceramic particles prior to mixing and / or casting the ceramic green body can cause the material adsorbed onto the alkali metal-containing ceramic particles to volatilize and / or reduce the amount of alkali metal on the surface of the alkali metal-containing ceramic particles. Mixing the alkali metal-containing ceramic particles with a solvent and optionally a dispersant (e.g., without additional materials) can provide good dispersion of the alkali metal-containing ceramic particles in the solvent (with little or no agglomerates), which can improve the dispersion and / or distribution of the alkali metal-containing ceramic particles during subsequent steps of the process. As discussed above, providing a dispersant can improve the dispersion and / or distribution of the alkali metal-containing ceramic particles, and / or can increase the time during which the dispersion of the alkali metal-containing ceramic particles can be maintained. Carbonate-based polymers can achieve increased processing speeds (e.g., faster debinding of the resulting ceramic green body) and / or increased quality of the resulting sintered article. Providing a viscosity modifier can achieve a second mixture with a predetermined viscosity, which can enable casting of the ceramic green body while achieving dimensional stability of the ceramic green body. Providing a reduced-pressure environment containing solvent can reduce solvent loss in the second mixture during degassing to form the precursor mixture. Providing a reduced-pressure environment can reduce dissolved gases in the second mixture, thereby providing a precursor mixture that can form a ceramic green body with a uniform, high-quality surface. Solvent annealing can produce a higher-quality ceramic green body with reduced defects, which can be used to form a higher-quality sintered product with fewer defects compared to what would be obtained without solvent annealing. In this aspect, the first oven 603 and the second oven 605 can be connected to each other and / or adjacent to each other, so that the temperature of the debonded ceramic product 201 does not drop significantly (e.g., about 100°C or less, about 50°C or less), which can reduce energy costs, processing time, and / or processing space requirements.

[0006] This disclosure also provides a solvent annealing apparatus including a solvent loading chamber configured to control the solvent removal rate of a solvent-containing ceramic green body. Solvent annealing can produce higher quality ceramic green bodies with reduced defects, which can be used to form higher quality sintered articles with fewer defects compared to those obtained without solvent annealing. The casting vapor pressure of the solvent provided in the casting chamber (e.g., about 100 Pascals or greater, about 1000 Pascals to about 50000 Pascals, and / or within 10000 Pascals of the boiling point vapor pressure of the solvent) can limit the amount of solvent evaporating from the solvent-containing ceramic green body during casting and / or in the casting chamber, which is related to the good surface quality of the resulting solvent-free ceramic green body and / or sintered article. Providing a chamber vapor pressure (e.g., about 20 Pascals or greater, about 1000 Pascals to about 50000 Pascals, and / or less than the casting vapor pressure) for the solvent in the solvent-loaded chamber can facilitate controlled removal of the solvent from the solvent-containing ceramic green body. Providing the solvent-containing ceramic green body with the temperature rise encountered during transport through the solvent-loaded ceramic green body can promote controlled and continuous removal of the solvent from the solvent-loaded ceramic green body as part of a solvent annealing process. Providing a drying vapor pressure of about 20 Pascals or less in the drying chamber can facilitate solvent removal from the solvent-containing ceramic green body to form a solvent-free ceramic green body. Providing an inlet at the distal end and an outlet at the proximal end of the drying chamber enables the atmosphere to flow in the opposite direction to the transport direction of the solvent-containing ceramic green body, which allows for continuous removal of the solvent from the solvent-containing ceramic green body as the atmosphere flows through and / or through the drying chamber. Furthermore, providing an outlet at the near end of the drying chamber allows for the removal of any solvent from the environment of the solvent-loaded chamber through orifice 1329. Introducing an atmosphere at both the far end and another location (between the far and near ends) can facilitate the removal of solvent from the solvent-containing ceramic green body at a predetermined rate. Providing an atmosphere with a low average velocity (e.g., about 0.1 m / s or less, or about 0.01 m / s to about 0.1 m / s) above the solvent-containing ceramic green body can contribute to uniform drying and / or a good surface quality of the resulting solvent-free ceramic green body and / or the resulting sintered article. The average velocity of the atmosphere above the solvent-containing ceramic green body can be lower than the average velocity of the atmosphere at other locations in the drying chamber, which can contribute to a high surface quality of the resulting article while allowing a larger volume of atmosphere exchange through the drying chamber 1331 to maintain a low chamber vapor pressure.

[0007] The following describes some exemplary aspects of this disclosure. It is to be understood that any feature of the various aspects may be used alone or in combination with each other.

[0008] Aspect 1: Ceramic green body, comprising, by weight percent of solvent-free ceramic green body:

[0009] From about 5% by weight to about 20% by weight of carbonate-based polymers;

[0010] Approximately 70% to approximately 95% by weight of alkali metal-containing ceramic particles;

[0011] 0% by weight to about 5% by weight of dispersant; and

[0012] 0% by weight to about 5% by weight of viscosity modifier.

[0013] Aspect 2: The ceramic green body of aspect 1, wherein the alkali metal-containing ceramic particles are lithium-containing ceramic particles.

[0014] Aspect 3: The ceramic green body of aspect 2, wherein the lithium-containing ceramic particles include: lithium cobalt oxide, lithium manganese oxide, lithium nickel manganese cobalt oxide, lithium nickel cobalt aluminum oxide, lithium iron phosphate, or combinations thereof.

[0015] Aspect 4: A ceramic green body of any one of Aspects 1-3, wherein the carbonate-based polymer is composed of alkyl carbonate esters.

[0016] Aspect 5: A ceramic green body of any one of Aspects 1-4, wherein the carbonate-based polymer is composed of: poly(ethylene carbonate), poly(propylene carbonate), poly(butylene carbonate), poly(cyclohexene carbonate), poly(propylene carbonate-co-cyclohexene carbonate), poly(propylene-co-cyclohexene carbonate), or a combination thereof.

[0017] Aspect 6: Ceramic green body of any one of Aspects 1-5, wherein the viscosity modifier includes dibutylcarboxylic acid ester.

[0018] Aspect 7: A ceramic green body of any one of Aspects 1-5, wherein the viscosity modifier includes: dibutyl phthalate, dibutyl adipate, dibutyl maleate, polyethylene glycol, or a combination thereof.

[0019] Aspect 8: A ceramic green body of any one of Aspects 1-7, wherein the thickness of the solvent-free ceramic green body ranges from about 5 micrometers to about 100 micrometers.

[0020] Aspect 9: Ceramic green bodies of any one of Aspects 1-8, wherein the median particle size of the alkali metal-containing ceramic particles is about 0.5 micrometers or smaller.

[0021] Aspect 10: A ceramic green body of any one of Aspects 1-9, wherein the weight ratio of the solvent-free ceramic green body to the solvent-containing ceramic green body is about 0.5 to about 0.7.

[0022] Aspect 11: Methods for forming sintered products, including:

[0023] The ceramic green body was heated to a maximum temperature of about 300°C or lower for a first period of time of about 4 minutes or less, during which heating removed about 70% by weight or more of the organic material from the ceramic green body; and then

[0024] The ceramic green body is sintered at a second temperature of about 700°C to about 1500°C for a second period of about 30 minutes to about 5 hours to form a sintered product having a relative density of about 90% or greater of the theoretical density.

[0025] The ceramic green body comprises a carbonate-based polymer and alkali metal-containing ceramic particles.

[0026] Aspect 12: The method of aspect 11, wherein heating removes approximately 90% or more of the organic material from the ceramic green body.

[0027] Aspect 13: The method of any one of Aspects 11-12, wherein the maximum temperature is about 260°C or lower, and the first time period is about 1 minute or less.

[0028] Aspect 14: The method of any one of Aspects 11-13, wherein the maximum heat flow from the ceramic green body during heating is about 2 W / g or less, in watts per gram of polymer in the ceramic green body (W / g).

[0029] Aspect 15: The method of any one of Aspects 11-14, wherein the thickness of the solvent-free ceramic green body ranges from about 5 micrometers to about 100 micrometers.

[0030] Aspect 16: The method of any one of Aspects 11-15, wherein, based on the weight percent of solvent-free ceramic green body, the ceramic green body comprises:

[0031] From about 5% by weight to about 20% by weight of carbonate-based polymers;

[0032] Approximately 70% to approximately 95% by weight of alkali metal-containing ceramic particles;

[0033] 0% by weight to about 5% by weight of dispersant; and

[0034] 0% by weight to about 5% by weight of viscosity modifier.

[0035] Aspect 17: The method of aspect 16, wherein the viscosity modifier includes dibutylcarboxylic acid ester.

[0036] Aspect 18: The method of any one of Aspects 11-15, further comprising:

[0037] Casting a solvent-containing ceramic green body from a precursor mixture, the solvent-containing ceramic green body having an initial thickness of about 5 micrometers to about 100 micrometers; and

[0038] Solvent annealing is performed on a solvent-containing ceramic green body to obtain a solvent-free ceramic green body.

[0039] Aspect 19: The method of aspect 18, wherein the weight ratio of the solvent-free ceramic green body to the solvent-containing ceramic green body is about 0.5 to about 0.7.

[0040] Aspect 20: The method of any one of Aspects 18-19, further comprising:

[0041] The alkali metal-containing ceramic particles are mixed with a solvent and optionally a dispersant to form a first mixture;

[0042] The first mixture is mixed with a carbonate-based polymer and optionally a viscosity modifier to form a second mixture; and

[0043] The second mixture is degassed in a reduced pressure environment for about 5 minutes or longer to form the precursor mixture.

[0044] Aspect 21: The method of any one of Aspects 18-19, wherein solvent annealing includes:

[0045] A solvent-containing ceramic green body is maintained in a solvent-loaded chamber, the solvent-loaded chamber containing the solvent in the solvent-containing ceramic green body, the chamber vapor pressure of the solvent in the solvent-loaded chamber being approximately 20 Pascals or higher, and the solvent-loaded chamber being maintained at a chamber temperature of 40°C or higher; and

[0046] The solvent-containing ceramic green body is dried in a drying chamber with a drying vapor pressure of about 20 Pascals or less and a drying temperature of about 70°C or higher.

[0047] Aspect 22: The method of aspect 21, wherein the chamber vapor pressure of the solvent in the solvent loading chamber is about 100 Pascals to about 50,000 Pascals.

[0048] Aspect 23: The method of any one of Aspects 21-22, wherein the drying temperature differs from the boiling point of the solvent by about 20°C.

[0049] Aspect 24: The method of any one of Aspects 21-23, wherein the casting of a solvent-containing ceramic green body is carried out in a casting chamber, the casting vapor pressure contained in the casting chamber being greater than or equal to the chamber vapor pressure of the solvent-loaded chamber.

[0050] Aspect 25: The method of any one of Aspects 11-24, wherein the alkali metal-containing ceramic particles are lithium-containing ceramic particles.

[0051] Aspect 26: The method of any one of Aspects 11-25, wherein the median particle size of the alkali metal-containing ceramic particles is about 0.5 micrometers or smaller.

[0052] Section 27: Solvent annealing equipment, including:

[0053] A casting chamber comprising casting apparatus configured to form a solvent-containing ceramic green body from a precursor mixture, the casting chamber being in fluid communication with a solvent reservoir;

[0054] A solvent loading chamber, comprising at least one heating device configured to maintain the temperature of the solvent loading chamber; and

[0055] A drying chamber, comprising a ventilation system configured to circulate an atmosphere from a substantially solvent-free environment through the drying chamber.

[0056] The solvent loading chamber is located between the casting chamber and the drying chamber, and is separated from the drying chamber by a baffle.

[0057] Aspect 28: The solvent annealing apparatus of Aspect 27, wherein the casting vapor pressure in the casting chamber of the solvent-containing ceramic green body is configured to be greater than or equal to the chamber vapor pressure in the solvent loading chamber, and the chamber vapor pressure is configured to be greater than the drying vapor pressure of the solvent in the drying chamber.

[0058] Aspect 29: A solvent annealing apparatus of any one of Aspects 27-28, wherein the ventilation system is configured to introduce an atmosphere from a substantially solvent-free environment at least at the far end of a baffled drying chamber opposite to the proximal end of the drying chamber, and the ventilation system is configured to remove the atmosphere from the drying chamber at the proximal end of the drying chamber.

[0059] Aspect 30: A solvent annealing apparatus of Aspect 29, wherein the drying chamber includes a plurality of orifices, the plurality of orifices including a first orifice at a distal end of the drying chamber and at least one additional orifice between the distal and proximal ends, the first orifice and the at least one additional orifice being configured to introduce an atmosphere from a substantially solvent-free environment.

[0060] Aspect 31: A solvent annealing apparatus of any one of Aspects 27-30, wherein the solvent loading chamber includes at least one additional solvent source.

[0061] Aspect 32: A method for forming a solvent-free ceramic green body, comprising:

[0062] Solvent-containing ceramic green bodies are obtained by casting from a precursor mixture, and the casting is carried out in a casting chamber containing a casting vapor pressure of about 100 Pascals or higher of the solvent in the solvent-containing ceramic green body.

[0063] The solvent-containing ceramic green body is transported from the casting chamber to the solvent loading chamber, wherein the solvent in the solvent loading chamber has a chamber vapor pressure of about 20 Pascals or higher, and the casting vapor pressure is greater than or equal to the casting vapor pressure.

[0064] The solvent-containing ceramic green body is heated at a chamber temperature of about 40°C or higher, where the chamber temperature of the solvent-loaded chamber is greater than that of the casting chamber.

[0065] The solvent-containing ceramic green body is transported from the solvent-loading chamber to the drying chamber, where the vapor pressure is greater than the drying vapor pressure of the solvent in the drying chamber; and

[0066] The solvent-containing ceramic green body is heated at the drying temperature in the drying chamber to form a solvent-free ceramic green body; the drying temperature is higher than the chamber temperature.

[0067] Aspect 33: The method of aspect 32, wherein the casting vapor pressure is maintained by a solvent reservoir in fluid communication with the casting chamber, and the solvent reservoir is heated to a reservoir temperature greater than the casting temperature of the casting chamber.

[0068] Aspect 34: The method of aspect 33, wherein the reservoir temperature is about 50°C to about 95°C.

[0069] Aspect 35: The method of any one of Aspects 32-34, wherein the casting vapor pressure is about 1,000 Pascals to about 50,000 Pascals.

[0070] Aspect 36: The method of any one of Aspects 32-35, wherein the solvent-containing ceramic green body is heated at the room temperature of the solvent-loaded chamber for about 3 minutes to about 10 minutes.

[0071] Aspect 37: The method of any one of Aspects 32-35 further includes introducing an atmosphere from a substantially solvent-free environment into the drying chamber at least at the distal end and removing the atmosphere from the drying chamber at the interface between the solvent-loaded chamber and the drying chamber at the proximal end, and the proximal end being the opposite of the distal end.

[0072] Aspect 38: The method of aspect 37, wherein the average velocity of the atmosphere above the solvent-containing ceramic green body in the drying chamber is about 0.01 m / s to about 0.1 m / s.

[0073] Aspect 39: The method of any one of Aspects 37-38, wherein atmosphere is introduced at the distal end and at least one additional location between the distal and proximal ends.

[0074] Aspect 40: The method of any one of Aspects 32-39, wherein the solvent includes: propylene glycol, methyl ethyl ketone, dimethyl carbonate, toluene, or a combination thereof.

[0075] Aspect 41: The method of any one of Aspects 32-40, wherein the solvent-containing ceramic green body has an initial thickness of about 5 micrometers to about 100 micrometers.

[0076] Aspect 42: The method of any one of Aspects 32-41, wherein the solvent-free ceramic green body comprises:

[0077] From about 5% by weight to about 20% by weight of carbonate-based polymers;

[0078] Approximately 70% to approximately 95% by weight of alkali metal-containing ceramic particles;

[0079] 0% by weight to about 5% by weight of dispersant; and

[0080] 0% by weight to about 5% by weight of viscosity modifier. Attached Figure Description

[0081] Referring to the accompanying drawings and reading the following detailed description, one can better understand the above-described features and advantages, as well as other features and advantages, in relation to this disclosure, wherein:

[0082] Figure 1 A schematic illustration of a ceramic green body according to the present disclosure;

[0083] Figure 2 This illustration shows sintered articles in accordance with the present disclosure.

[0084] Figure 3 The heating of alkali metal-containing ceramic particles is shown as part of an exemplary method.

[0085] Figure 4 The mixing and degassing process shown as part of an exemplary method is used to form a precursor solution;

[0086] Figure 5 The annealing of ceramic green bodies is shown as part of an exemplary method;

[0087] Figure 6 This demonstrates debonding and sintering as part of an exemplary method;

[0088] Figure 7 The flowchart illustrates an exemplary method for forming sintered products;

[0089] Figure 8 Show the mass loss curves from thermogravimetric analysis (TGA);

[0090] Figure 9 Display the heat flow profile from differential scanning calorimetry (DSC);

[0091] Figure 10 The mass loss curves of poly(vinyl butyral) (PVB) and poly(propylene-co-cyclohexylene carbonate) (PPCC) polymers from TGA are shown.

[0092] Figure 11 Showing the mass loss curves of ceramic green bodies from TGA;

[0093] Figure 12 Displaying the heat flow profile of the ceramic green body from DSC;

[0094] Figure 13 A schematic diagram of solvent annealing equipment; and

[0095] Figure 14 It is along Figure 13 A cross-sectional view of line 14-14.

[0096] Throughout this disclosure, the accompanying drawings are used to emphasize certain aspects. Therefore, unless otherwise expressly stated, it should be assumed that the relative dimensions of the different regions, portions, and substrates shown in the drawings are not proportional to their actual relative dimensions. Detailed Implementation

[0097] The aspects will be described more fully herein with reference to the accompanying drawings, in which exemplary aspects are shown. Wherever possible, the same reference numerals are used in all the drawings to denote the same or similar parts.

[0098] According to the aspects of this disclosure, Figure 1 The image shows a ceramic green body 101 comprising a carbonate-based polymer, and Figure 2 This shows a sintered article 201 that can be manufactured from the ceramic green body 101. Unless otherwise stated, the discussion of features of one aspect of the ceramic green body is equivalent to the discussion of corresponding features of any aspect of this disclosure. For example, throughout this disclosure, the same part numbers may indicate that, in some aspects, the referred features are consistent with each other, and unless otherwise stated, the discussion of features referred to in one aspect is equivalent to the discussion of features referred to in any other aspect of this disclosure.

[0099] Figure 1 The ceramic green body 101 is shown, comprising a first main surface 105 and a second main surface 107 opposite to the first main surface 105. In this aspect, the first main surface 105 and / or the second main surface 107 may extend along corresponding planes, and / or the first main surface 105 may be substantially parallel to the second main surface 107. The green body thickness 109 is defined as the average distance between the first main surface 105 and the second main surface 107. In this aspect, the green body thickness 109 may be: about 5 micrometers (μm) or greater, about 10 μm or greater, about 20 μm or greater, about 30 μm or greater, about 100 μm or less, about 80 μm or less, about 60 μm or less, or about 50 μm or less. In this respect, the thickness 109 of the green body can be in the range of about 5 μm to about 100 μm, about 10 μm to about 80 μm, about 20 μm to about 60 μm, about 30 μm to about 50 μm, or any range or subrange therebetween.

[0100] like Figure 1 As shown, the ceramic green body 101 comprises a plurality of ceramic particles 111 dispersed in a binder system 113. In one aspect, the plurality of ceramic particles includes alkali metal-containing ceramic particles. As used herein, "alkali metal" refers to lithium, sodium, potassium, rubidium, cesium, francium, or combinations thereof. It is not intended to limit one's understanding that alkali metal-containing ceramic particles may cause debonding problems (i.e., removal of the organic components of the ceramic green body) within a short period of time (e.g., about 4 minutes or less) because alkali metals can catalyze the chain scission of potentially flammable components (e.g., polymers) in the binder system, which could damage the ceramic and / or the resulting sintered article. In other aspects, the alkali metal-containing ceramic particles may include lithium-containing ceramic particles. Exemplary aspects of lithium-containing ceramic particles include: lithium cobalt oxide, lithium manganese oxide, lithium nickel manganese cobalt oxide, lithium nickel cobalt aluminum oxide, lithium iron phosphate, or combinations thereof.

[0101] Throughout this disclosure, the “particle size” of ceramic particles is determined by direct imaging using a scanning electron microscope (SEM), wherein the largest scale of the ceramic particle is taken as the particle size. In this aspect, the median particle size of the alkali metal-containing ceramic particles can be: about 10 μm or less, about 5 μm or less, about 2 μm or less, about 1 μm or less, or about 0.5 μm or less, for example, the following ranges: 0.01 μm to about 10 μm, about 0.05 μm to about 5 μm, about 0.1 μm to about 1 μm, about 0.2 μm to about 0.5 μm, or any range or subrange thereof.

[0102] Throughout this disclosure, "by weight percent of solvent-free ceramic green body" means the weight percentage (wt%) of the ceramic green body ignoring any contribution from solvents. In this aspect, by weight percent of solvent-free ceramic green body, the ceramic green body may contain alkali metal-containing ceramic particles in the following amounts: about 70 wt% or more, about 73 wt% or more, about 75 wt% or more, about 76 wt% or more, about 77 wt% or more, about 78 wt% or more, about 95 wt% or less, 93 wt% or less, about 90 wt% or less, about 85 wt% or less, about 84 wt% or less, about 83 wt% or less, or about 82 wt% or less. In this respect, the ceramic green body containing alkali metal ceramic particles may be in the following range, based on the weight percentage of solvent-free ceramic green body: about 70% to about 95% by weight, about 73% to about 93% by weight, about 75% to about 90% by weight, about 76% to about 85% by weight, about 77% to about 84% by weight, about 78% to about 83% by weight, about 78% to about 82% by weight, or any range or subrange thereof.

[0103] Binder system 113 includes carbonate-based polymers. As used herein, a "carbonate-based polymer" contains carbonate esters having an R1-OC(O)-O-R2 structure along the backbone of the repeating unit (i.e., monomer), wherein R1 and R2 may be organic groups. In this aspect, R1 may be omitted, having R2 comprising an organic group, for example, the repeating unit extending from the leftmost oxygen through R2, or R2 may be omitted while R1 comprises an organic unit. Throughout this disclosure, an "organic group" consists of atoms selected from the group consisting of carbon, hydrogen, oxygen, nitrogen, sulfur, phosphorus, chlorine, and bromine. In this aspect, carbonate-based polymers may consist of atoms selected from the group consisting of carbon, hydrogen, and oxygen. Throughout this disclosure, the "backbone" of a repeating unit refers to the longest atomic chain extending from one bond defining the repeating unit to another bond defining the repeating unit at the other end. Throughout this disclosure, the "backbone" of a polymer refers to the longest atomic chain extending from one end of the polymer to the other end. In this aspect, carbonate-based polymers may include linear polymers. As used herein, a “linear polymer” includes repeating units connected to only one or two other repeating units, such that all repeating units form a continuous chain from one end of the polymer to the other.

[0104] In some aspects, carbonate-based polymers may include homopolymers. As used herein, a “homogeneous polymer” consists of a single repeating unit that forms the homopolymer. Exemplary aspects of homopolymer-based carbonate polymers include: polycarbonate, poly(ethylene carbonate), poly(propylene carbonate), poly(butylene carbonate), poly(pentamethylene carbonate), poly(hexamethylene carbonate), poly(cyclopentamethylene carbonate), and poly(cyclohexylene carbonate). In other aspects, the binder system may consist of alkyl carbonate esters in the polymerized form of repeating units. As used herein, “alkyl” refers to an unsaturated (i.e., without double bonds) functional group consisting of a combination of carbon, hydrogen, and / or oxygen. For example, alkyl groups include linear C1-C... 20 Compounds, cyclic C5-C 10 Compounds, and combinations thereof. Alkyl carbonate esters have no double bonds other than carbonate. Exemplary aspects of polymers based on linear alkyl carbonates include: poly(ethylene carbonate), poly(propylene carbonate), poly(butyl carbonate), poly(pentamethylene carbonate), and poly(hexamethylene carbonate). Exemplary aspects of polymers based on cycloalkyl carbonates include poly(cyclopentane carbonate) and poly(cyclohexane carbonate). In these aspects, carbonate-based polymers may include copolymers. As used herein, a “copolymer” includes two or more distinct repeating units (i.e., comonomers) that repeat to form a homopolymer. The copolymer may be a block copolymer, an alternating copolymer (e.g., ABAB), or a random copolymer, where each repeating unit has a different block. In these aspects, one comonomer comprises a carbonate and the other comonomer is an alkyl chain. In other aspects, one comonomer comprises an alkyl carbonate and the other comonomer is an alkyl chain. Exemplary aspects of carbonate-based copolymers are poly(propylene carbonate-co-cyclohexylene carbonate) and poly(propylene-co-cyclohexylene carbonate). Exemplary aspects of carbonate-based polymers include: poly(ethylene carbonate), poly(propylene carbonate), poly(butylene carbonate), poly(cyclohexylene carbonate), poly(propylene carbonate-co-cyclohexylene carbonate), poly(propylene-co-cyclohexylene carbonate), or combinations thereof.

[0105] Providing carbonate-based polymers enables faster processing of the resulting ceramic green bodies to form sintered articles, for example, by reducing the occurrence of events that could compromise the quality of the sintered article during the heating of the ceramic green body. For instance, carbonate-based polymers can provide reduced flammability during the heating of the ceramic green body. Flammability is associated with larger molecular weights (e.g., 200 Daltons or greater) corresponding to the bonding of multiple monomers, which can result in decomposition during heating, for example, as a result of chain scission. It is not desirable to be limited by theory that carbonate-based polymers and acrylate-based polymers (e.g., methacrylate-based polymers) decompose via depolymerization in addition to chain scission, while other polymers decompose only via chain scission. However, as demonstrated by the examples below, in the presence of alkali metal-containing ceramic particles, it was unexpectedly found that methacrylate-based polymers decompose primarily via chain scission, while carbonate-based polymers decompose primarily via depolymerization.

[0106] Throughout this disclosure, the “molecular weight” of the polymer chain is measured using high-performance liquid chromatography (HPLC) calibrated to polystyrene (PS) standards. As used herein, the term “molecular weight” refers to the number-average molecular weight (Mn). The number-average molecular weight is calculated by summing the products of the molecular weight and the fraction of the polymer that has that molecular weight. In this respect, the molecular weight of the polycarbonate-based polymer (e.g., in ceramic green bodies) can be: about 50,000 Daltons (Da) or greater, about 100,000 Da or greater, about 120,000 Da or greater, about 500,000 Da or less, about 300,000 Da or less, about 250,000 Da or less, or about 200,000 Da or less, for example, the range of about 50,000 Da to about 500,000 Da, about 100,000 Da to about 300,000 Da, about 100,000 Da to about 250,000 Da, or any range or subrange thereof.

[0107] In this aspect, the amount of carbonate-based polymer contained in the solvent-free ceramic green body may be, based on the following percentages by weight: about 5% by weight or more, about 10% by weight or more, about 12% by weight or more, about 15% by weight or more, about 20% by weight or less, about 19% by weight or less, about 18% by weight or less, or about 17% by weight or less. In this aspect, the amount of carbonate-based polymer contained in the solvent-free ceramic green body may be, based on the following percentages by weight: about 5% by weight to about 20% by weight, about 10% by weight to about 19% by weight, about 12% by weight to about 18% by weight, about 15% by weight to about 17% by weight, or any range or subrange thereof.

[0108] In this aspect, the binder system 113 may include a dispersant. As used herein, "dispersant" refers to a material that improves particle separation, improves the uniformity of particle distribution, reduces particle agglomeration, and / or reduces particle sedimentation. In this aspect, the dispersant may include fish oil or commercially available dispersants, such as the Hypermer dispersant product line (available from Croda Energy Technologies). In this aspect, the dispersant contained in the ceramic green body, based on the weight percentage of the solvent-free ceramic green body, may be in the following amounts: 0% by weight or more, greater than 0% by weight or more, about 0.5% by weight or more, about 1% by weight or more, about 1.1% by weight or more, about 1.2% by weight or more, about 5% by weight or less, about 3% by weight or less, about 2% by weight or less, or about 1.5% by weight or less, or about 1.3% by weight or less. In this aspect, the dispersant contained in the ceramic green body, based on a weight percentage of the solvent-free ceramic green body, can be in the following ranges: 0% to about 5% by weight, greater than 0% to about 5% by weight, about 0.5% to about 3% by weight, about 1% to about 2% by weight, about 1.1% to about 1.5% by weight, about 1.2% to about 1.3% by weight, or any range or subrange thereof. Alternatively, in this aspect, the binder system 113 may be free of dispersant.

[0109] In one aspect, the binder system 113 may include a viscosity modifier. In another aspect, the viscosity modifier may increase the viscosity of the resulting mixture. In another aspect, the viscosity modifier may include dibutyl carboxylate. Exemplary aspects of the viscosity modifier include: dibutyl phthalate, dibutyl adipate, dibutyl maleate, polyethylene glycol, and combinations thereof. In other aspects, the viscosity modifier may include dibutyl phthalate. In another aspect, the viscosity modifier contained in the ceramic green body, based on the weight percentage of the solvent-free ceramic green body, may be in the following amounts: 0% by weight or more, greater than 0% by weight or more, about 0.5% by weight or more, about 1% by weight or more, about 1.5% by weight or more, about 5% by weight or less, about 4% by weight or less, or about 3% by weight or less, about 2.5% by weight or less, or about 2% by weight or less. In this aspect, the viscosity modifier contained in the ceramic green body, based on the weight percentage of the solvent-free ceramic green body, can be in the following range: 0% to about 5% by weight, greater than 0% to about 4% by weight, about 0.5% to about 3% by weight, about 1% to about 2.5% by weight, about 1.5% to about 2% by weight, or any range or subrange thereof. Alternatively, in this aspect, the binder system 113 may be free of viscosity modifier.

[0110] In one aspect, the ceramic green body may contain a solvent. For example, the ceramic green body may be formed from a precursor mixture that serves as a solvent-containing ceramic green body. In other aspects, the solvent may include aprotic solvents, such as polar aprotic solvents. Exemplary aspects of the solvent include: dimethyl carbonate, methyl ethyl ketone, toluene, anisole, dioxolane, methoxypropyl acetate, and combinations thereof. In one aspect, the weight ratio of the solvent-free ceramic green body to (e.g., freshly formed) solvent-containing ceramic green body may be: about 0.5 or greater, about 0.55 or greater, about 0.58 or greater, about 0.7 or less, about 0.65 or less, or about 0.63 or less. In another aspect, the weight ratio of the solvent-free ceramic green body to (e.g., freshly formed) solvent-containing ceramic green body may be in the range of about 0.5 to about 0.7, about 0.55 to about 0.65, about 0.58 to about 0.63, or any range or subrange thereof.

[0111] Table 1 presents exemplary ranges R1-R5 of the composition of a solvent-free ceramic green body (e.g., ceramic green body 101) according to the aspects discussed in the preceding paragraphs. Range R1 corresponds to the widest range, while ranges R2-R5 are sub-ranges therein. Range R2 is free of viscosity modifiers. Ranges R1-R3 may be free of dispersants, while ranges R1-R5 may contain dispersants. Range R5 provides the narrowest range among ranges R1-R5. In this aspect, all polymers in the binder system 113 may be carbonate-based polymers. In this aspect, the binder system 113 may consist of carbonate-based polymers, alkali metal-containing ceramic particles, dispersants, optionally viscosity modifiers, and optionally solvents.

[0112] Table 1: Composition of solvent-free ceramic green bodies (wt%)

[0113]

[0114]

[0115] Figure 2The sintered article 201 is shown, comprising a first main surface 205 and a second main surface 207 opposite to the first main surface 205. In this aspect, the first main surface 205 and / or the second main surface 207 may extend along corresponding planes, and / or the first main surface 205 may be substantially parallel to the second main surface 207. The sintering thickness 209 is defined as the average distance between the first main surface 205 and the second main surface 207. In this aspect, the sintering thickness 209 may be within one or more of the ranges discussed above with respect to the green body thickness 109. The sintered article 201 comprises sintered ceramic 211, such as ceramic particles 111 corresponding to alkali metals. In this disclosure, the “relative density” of the sintered article refers to the percentage of the maximum density obtained from a fully densified pure material composed of the same ceramic material. In this aspect, the sintered article 201 may include a relative density of about 80% or greater, about 85% or greater, about 90% or greater, about 92% or greater, or about 95% or greater.

[0116] In one aspect, the sintered article can be an electrode that is part of a battery. For example, the sintered article can be a cathode disposed on an electrolyte (e.g., a solid electrolyte), which in turn is disposed on an anode to form a battery (e.g., a solid-state battery). Alternatively, in another aspect, the sintered article can be integrated into a display device, for example, as a protective cover.

[0117] Reference Figure 7 The flowchart and Figure 3-6 The exemplary method steps shown herein are used to discuss a method for manufacturing sintered articles or ceramic green bodies according to the present disclosure. In the first step 701, the method may begin by obtaining alkali metal-containing ceramic particles, a carbonate-based polymer, and optionally a dispersant and / or a viscosity modifier. In one aspect, the alkali metal-containing ceramic particles can be provided by purchasing or otherwise obtaining them. In other aspects, the alkali metal-containing ceramic particles can be obtained by forming a glass that can be heat-treated to form one or more ceramic crystals; then the alkali metal-containing ceramic material can be ground to obtain particles of a predetermined particle size. In another aspect, the carbonate-based polymer and / or solvent can be provided by purchasing or otherwise obtaining them. Similarly, if obtained in step 701, the dispersant and / or viscosity modifier can be provided by purchasing or otherwise obtaining them. In one aspect, at the end of step 701, a ceramic green body comprising a carbonate-based polymer and alkali metal-containing ceramic particles may be formed or obtained by any other means; however, in other aspects, the ceramic green body may be formed after steps 703, 705, 707, 709, 711 and / or 713, as discussed below.

[0118] After step 701, as Figure 3 As shown, the method can proceed to step 703, which includes heating the alkali metal-containing ceramic particles 111 at a first temperature for a first time period. In this aspect, as Figure 3 As shown, heating the alkali metal-containing ceramic particles 111 may include placing the alkali metal-containing ceramic particles 111 in an oven 301 maintained at a first temperature for a first time period. In this aspect, the first temperature may be: about 150°C or higher, about 300°C or higher, about 600°C or higher, about 900°C or higher, about 1200°C or lower, about 1000°C or lower, about 700°C or lower, or about 250°C or lower, for example, the ranges from about 150°C to about 1200°C, about 600°C to about 1000°C, about 900°C to about 1000°C, or any range or subrange thereof. In this aspect, the first time period may be: about 1 minute or longer, about 5 minutes or longer, about 20 minutes or shorter, or about 10 minutes or shorter, for example, about 1 minute to about 20 minutes, about 5 minutes to about 10 minutes, or any range or subrange thereof. Heating the alkali metal-containing ceramic particles prior to steps 703, 705, 707, and 709 (e.g., mixing and / or casting the ceramic green body) can cause the material adsorbed onto the alkali metal-containing ceramic particles to volatilize and / or reduce the amount of alkali metal on the surface of the alkali metal-containing ceramic particles.

[0119] After step 701 or 703, as Figure 4 As shown, the method can proceed to step 705, which includes mixing alkali metal-containing ceramic particles 111 with a solvent and optionally a dispersant to form a first mixture 421. In this aspect, as Figure 4As shown, when the first mixture 421 containing the dispersion medium 413 is in the container 411, the first mixture 421 can be mixed using a stirrer 407 rotating 409 about a shaft 406. In this aspect, step 705 may include mixing the material for a second time period: about 4 hours or longer, about 12 hours or longer, about 16 hours or longer, about 1 day or longer, about 30 days or less, about 4 days or less, or about 3 days or less. In this aspect, step 705 may include mixing the material for a second time period ranging from about 4 hours to about 30 days, about 12 hours to about 4 days, about 16 hours to about 3 days, about 1 day to about 3 days, or any range or subrange thereof. In this aspect, mixing may be performed at a second temperature of about 100°C or lower, or about 60°C or lower, for example: about 20°C to about 100°C, about 25°C to about 60°C, about 25°C to about 40°C, or any range or subrange thereof. Mixing alkali metal-containing ceramic particles with a solvent and optionally a dispersant (e.g., without additional materials) can provide good dispersion of the alkali metal-containing ceramic particles in the solvent (with little or no agglomerates), which can improve the dispersion and / or distribution of the alkali metal-containing ceramic particles during subsequent steps. As discussed above, providing a dispersant can improve the dispersion and / or distribution of the alkali metal-containing ceramic particles, and / or can increase the time during which the dispersion of the alkali metal-containing ceramic particles can be maintained.

[0120] After step 705, as Figure 4 As shown, the method can proceed to step 707, which includes mixing the first mixture 421 with a carbonate-based polymer and optionally a viscosity modifier to form a second mixture 423. In aspects, as Figure 4 As shown, when the second mixture 421 containing the dispersion medium 413 is in the container 411, the second mixture 423 can be mixed using a stirrer 407 rotating 409 about the shaft 406. In one aspect, step 707 may include mixing for a third time period, falling within one or more of the ranges discussed in the preceding paragraphs regarding the second time period in step 705, for example, about 12 hours to about 3 days. In another aspect, step 707 may include a third temperature falling within one or more of the ranges discussed in the preceding paragraphs regarding the second temperature in step 705. As discussed above, carbonate-based polymers can achieve increased processing speed (e.g., faster debinding of the resulting ceramic green body) and / or increased quality of the resulting sintered product. Providing a viscosity modifier can achieve a second mixture with a predetermined viscosity, which allows for casting of the ceramic green body while achieving dimensional stability.

[0121] After step 707, as Figure 4As shown, the method can proceed to step 709, which includes degassing the second mixture to form a precursor mixture. In one aspect, degassing may include subjecting the second mixture to a reduced pressure environment for a third time period. As used herein, a "reduced pressure environment" has an absolute pressure of less than 80 kPa. In other aspects, the reduced pressure environment may include an absolute pressure ranging from about 1 kPa to about 80 kPa, about 5 kPa to about 50 kPa, about 10 kPa to about 30 kPa, or any range or subrange thereof. In other aspects, the third time period may be about 1 minute or longer, about 5 minutes or longer, about 30 minutes or shorter, or about 10 minutes or shorter, for example: about 1 minute to about 30 minutes, about 5 minutes to about 10 minutes, or any range or subrange thereof. In other aspects, the reduced pressure environment may contain a solvent corresponding to the solvent in the precursor mixture. In one aspect, as Figure 4 As shown, the second mixture 423 in container 411 is placed in a vacuum chamber 401 connected to a vacuum pump 405 via a valve 403, where depressurization in the vacuum chamber 401 degasses the second mixture 423 to form a precursor mixture 425. In other aspects, as shown, another container 431 containing a solvent 433 corresponding to the solvent in the second mixture 423 may also be in the vacuum chamber 401, for example, to reduce solvent evaporation from the second mixture 423 during step 709. Providing a depressurized environment containing the solvent can reduce solvent loss from the second mixture during step 709. Providing a depressurized environment can reduce dissolved gases in the second mixture, thereby providing a precursor mixture that can form a ceramic green body with a uniform, high-quality surface.

[0122] After step 701 or 709, as Figure 5 As shown, the method can proceed to step 711, which includes casting a precursor solution to form a solvent-containing ceramic green body 501 comprising an initial thickness 509. In this aspect, the initial thickness 509 may be within one or more ranges discussed above with respect to the green body thickness 109. The solvent-containing ceramic green body 501 may include the components described above. Figure 1 One or more details of the ceramic green body 101 discussed. In this regard, reference may be made below. Figure 13 The casting apparatus 1311 in the solvent annealing apparatus 1301 discussed herein is used to produce a solvent-containing ceramic green body.

[0123] After step 701 or 711, as Figure 5As shown, the method can proceed to step 713, which includes solvent annealing of the solvent-containing ceramic green body 501 to form the ceramic green body 101. As used herein, "solvent annealing" refers to controlling (i.e., reducing) the rate at which the solvent leaves the solvent-containing ceramic green body by providing an appropriate concentration of solvent in the environment surrounding the solvent-containing ceramic green body. In aspects, such as Figure 5 As shown, the solvent-containing ceramic green body 501 can be placed in a container 511 (e.g., a vacuum chamber) with a controlled environment, wherein the solvent concentration in the environment can be controlled (e.g., via valves 503 and 513). Alternatively, the solvent concentration in the environment can be maintained and / or increased by allowing vapor from a reservoir of solvent 433, which is in fluid communication with a solvent source via conduit 507, by opening valve 513. Alternatively, a solvent reservoir may not be present during solvent annealing. In other aspects, as shown, the solvent concentration can be maintained and / or decreased by adjusting valve 503, which can be connected to pump 505, which can be used to control the pressure in container 511. Alternatively, solvent annealing can be performed by covering the solvent-containing ceramic green body with a material that is semi-permeable to the solvent or impermeable to the solvent. At the end of step 713, the ceramic green body 101 may include one or more aspects (e.g., composition) discussed above regarding ceramic green bodies. In this aspect, solvent annealing can be performed for: about 10 minutes or longer, about 30 minutes or longer, about 1 hour or longer, about 2 hours or longer, about 3 hours or longer, about 24 hours or less, about 8 hours or less, about 5 hours or less, about 4 hours or less, about 2 hours or less, or about 1 hour or less, for example: about 10 minutes to about 24 hours, about 30 minutes to about 8 hours, about 1 hour to about 8 hours, about 2 hours to about 5 hours, about 3 hours to about 4 hours, or any range or subrange therebetween. In this aspect, solvent annealing can be performed at room temperature (i.e., 25°C) (e.g., about 20°C to about 30°C). In this respect, solvent annealing can be performed under reduced pressure corresponding to the following absolute pressures: about 1 kPa or greater, about 5 kPa or greater, about 50 kPa or less, about 20 kPa or less, or about 10 kPa or less, for example: about 1 kPa to about 50 kPa, about 5 kPa to about 20 kPa, about 5 kPa to about 10 kPa, or any range or subrange thereof. Solvent annealing can produce higher quality ceramic green bodies with reduced defects, which can be used to form higher quality sintered articles with reduced defects compared to those obtained without solvent annealing. In this respect, reference can be made to the following: Figure 13 Solvent annealing is performed in the solvent loading chamber 1321 of the solvent annealing apparatus 1301 as described above.

[0124] After steps 701, 711, or 713, such as Figure 6 As shown, the method can proceed to step 715, which includes heating the ceramic green body 101 at a fifth temperature for a fifth time period. In one aspect, as shown, step 715 may include heating the ceramic green body 101 using one or more heaters 604a and / or 604b (e.g., in a first oven 603). In other aspects, as shown, the ceramic green body may be conveyed in direction 602 through the one or more heaters 604a and / or 604b (e.g., through the first oven 603), which allows for continuous processing of the ceramic green body 101. In one aspect, the fifth temperature may be: about 300°C or lower, about 280°C or lower, about 260°C or lower, about 250°C or lower, about 100°C or higher, about 150°C or higher, about 200°C or higher, or about 220°C or higher. In this aspect, the fifth temperature can be a range of approximately 100°C to approximately 300°C, approximately 150°C to approximately 280°C, approximately 200°C to approximately 260°C, approximately 220°C to approximately 250°C, or any range or subrange thereof. For example, in step 715, the maximum temperature at which the ceramic green body 101 is heated can be approximately 300°C or lower, approximately 280°C or lower, approximately 260°C or lower, or approximately 250°C or lower. In this aspect, as step 715 proceeds, the temperature at which the ceramic green body 101 is heated can be increased, for example, by a linear increase or by increasing a continuous temperature zone having a corresponding predetermined temperature. In this aspect, the fifth time period can be approximately 4 minutes or less, approximately 3 minutes or less, approximately 2 minutes or less, or approximately 1 minute or less, approximately 15 seconds or more, approximately 20 seconds or more, approximately 30 seconds or more, approximately 40 seconds or more, or approximately 1 minute or more. In this context, the fifth time period can be within the following ranges: approximately 15 seconds to approximately 5 minutes, approximately 20 seconds to approximately 4 minutes, approximately 20 seconds to approximately 3 minutes, approximately 30 seconds to approximately 2 minutes, approximately 40 seconds to approximately 1 minute, or any range or subrange thereof. Step 715 is configured to remove organic material from the ceramic green body to produce a debonded ceramic article 611 comprising alkali metal-containing ceramic particles 111 and cavities formed by the organic material removed in step 715 (see [link to article]). Figure 6In this aspect, step 715 can remove about 70% by weight or more, about 80% by weight or more, about 85% by weight or more, about 90% by weight or more, or about 95% by weight or more of organic material from the ceramic green body 101. As discussed herein, due to the composition of the binder system 113 (e.g., a carbonate-based polymer), the removal of organic material in step 715 can be carried out faster and / or at a lower temperature than in any other possible scenario. Specifically, the binder system 113, combined with alkali metal-containing ceramic particles 111, can have reduced flammability compared to other materials used in binder systems having the same alkali metal-containing ceramic particles, which can enable the formation of high-quality sintered articles and / or faster removal of organic material. Faster removal of organic material can increase yield and minimize resources (e.g., energy for heating, space for heating, time).

[0125] Throughout this disclosure, thermogravimetric analysis and differential scanning calorimetry (DSC) are used to measure “heat flow” and “mass loss” at a heating rate of 10 °C / min. As used herein, positive heat flow refers to exothermic behavior (i.e., the release of heat from the sample). In this aspect, the maximum heat flow of the ceramic green body from 25 °C to 300 °C can occur at temperatures of approximately 200 °C or higher, approximately 230 °C or higher, approximately 240 °C or higher, approximately 300 °C or lower, approximately 290 °C or lower, or approximately 270 °C or lower. In this aspect, the maximum heat flow of the ceramic green body from 25 °C to 300 °C can occur within the following temperature ranges: approximately 200 °C to approximately 300 °C, approximately 230 °C to approximately 290 °C, approximately 240 °C to approximately 270 °C, or any range or subrange thereof. In this aspect, the maximum heat flux of the ceramic green body (in watts (W / g) emitted per gram of ceramic cell from the ceramic green body (exothermic) at 25°C to 300°C) can be about 1 W / g to about 7 W / g, about 3 W / g to about 6 W / g, or any range or subrange therebetween. In this aspect, the maximum heat flux of the ceramic green body (in watts (exothermic) emitted per gram of polymer in the ceramic cell (W / g)) from 25°C to 300°C can be: about 2.5 W / g or less, 2 W / g or less, about 1 W / g or more, or about 1.5 W / g or more, for example: about 1 W / g to about 2.5 W / g, about 1.5 W / g to about 2 W / g, or any range or subrange therebetween. Providing reduced heat flux (e.g., about 7 W / g ceramic green body or less, about 2 W / g polymer in ceramic green body) can reduce the probability of introducing defects during step 715, such as flammability from runaway thermal decomposition or polymer decomposition, and / or can enable faster ceramic green body processing while maintaining high quality of the resulting sintered product.

[0126] After step 715, as Figure 6 As shown, the method can proceed to step 717, including heating at a sixth temperature for a sixth time period. In one aspect, as shown, the debonded ceramic article 611 can be heated (e.g., in a second oven 605) by one or more heaters 606a and / or 606b to form a sintered article 201 containing sintered ceramic 211. In other aspects, as shown, the debonded ceramic article 611 can be conveyed in direction 608 through the one or more heaters 606a and / or 606b (e.g., through the second oven 605), which allows for continuous processing to form the sintered article 201. In another aspect, as shown... Figure 6 As shown, the processing equipment 601 may include a first oven 603 and a second oven 605 arranged sequentially along a movement path (see arrow 602 or direction 608) along which the ceramic green body 101 moves. In other respects, the first oven 603 and the second oven 605 may be connected to each other and / or closely adjacent (e.g., adjacent) so that the temperature of the debonded ceramic article 611 does not drop significantly (e.g., about 100°C or less, about 50°C or less), which can reduce energy costs, processing time, and / or the space required for processing. Between the first oven 603 and the second oven 605, the temperature increases sharply (e.g., by about 100°C or more, about 300°C or more, about 100°C / min or higher, or about 300°C / min or higher). In this aspect, the sixth temperature can be: about 700°C or higher, about 800°C or higher, about 900°C or higher, about 1500°C or lower, about 1300°C or lower, or about 1100°C or lower. In this aspect, the sixth temperature can be a range of about 700°C to about 1500°C, about 800°C to about 1300°C, about 900°C to about 1100°C, or any range or subrange thereof. In this aspect, the sixth time period can be: about 15 minutes or longer, about 30 minutes or longer, about 45 minutes or longer, about 1 hour or longer, about 5 hours or less, about 3 hours or less, about 2 hours or less, about 1.5 hours or less, or about 1 hour or less. In this aspect, the sixth time period can be a range of about 15 minutes to about 5 hours, about 30 minutes to about 3 hours, about 45 minutes to about 2 hours, about 1 hour to about 1.5 hours, or any range or subrange thereof. Sintering the debonded ceramic article 611 in step 717 can densify the debonded ceramic article 611 and / or give it mechanical strength. At the end of step 717, the sintered article 201 may include a relative density and / or thickness falling within one or more corresponding ranges discussed above with respect to the sintered article 201.

[0127] Following step 717, the method may proceed to step 719, which includes assembling a sintered article into the composite article. In one aspect, the sintered article may be an electrode that is part of a battery. For example, the sintered article may be a cathode disposed on an electrolyte (e.g., a solid electrolyte), which in turn is disposed on an anode to form a battery (e.g., a solid-state battery). In another aspect, the sintered article may be integrated into a consumer electronic device (e.g., a display device), for example, as a protective cover.

[0128] After steps 715, 717, or 719, the method can be completed after reaching step 721. In this aspect, the steps discussed above can be followed sequentially. Figure 7 The method for manufacturing a sintered article or ceramic green body according to the present disclosure is performed by steps 701, 703, 705, 707, 709, 711, 713, 715, 717, 719, and 721 in the flowchart. In one aspect, the method may proceed from step 701 to step 705 along arrow 702, for example, if the alkali metal-containing ceramic particles are not to be heated before mixing, or if the alkali metal-containing ceramic particles have already been treated before the end of step 701. In another aspect, the method may proceed from step 701 to step 715 along arrow 704, for example, if the alkali metal-containing ceramic particles are already a portion of the ceramic green body that will not subsequently undergo solvent annealing at the end of step 701. In yet another aspect, the method may proceed from step 701 to step 711 along arrow 706, for example, if the alkali metal-containing ceramic particles are in a precursor solution at the end of step 701. In one aspect, the method may proceed from step 701 to step 713 along arrow 708, for example, if the alkali metal-containing ceramic particles are already part of a solvent-containing ceramic green body and the ceramic green body will undergo solvent annealing in step 713. In another aspect, the method may proceed from step 711 to step 715 along arrow 710, for example, if the solvent-containing ceramic green body is to be heated without prior solvent annealing. In another aspect, the method may proceed from step 715 to step 721 along arrow 712, for example, if the method is completed at the end of step 715. In another aspect, the method may proceed from step 717 to step 721 along arrow 714, for example, if the method is completed at the end of step 717. Any of the above options may be combined to manufacture sintered articles or ceramic green bodies according to embodiments of this disclosure.

[0129] Figure 13A solvent annealing apparatus 1301 according to an aspect of this disclosure is schematically shown. As shown, the solvent annealing apparatus 1301 includes a casting chamber 1309 comprising a casting apparatus 1311. The casting apparatus 1311 is configured to form a solvent-containing ceramic green body 1328 from a precursor mixture (e.g., casting the precursor mixture to form a solvent-containing ceramic green body). In one aspect, as shown, the solvent annealing apparatus 1301 may optionally include an adapter 1313 configured to transfer the solvent-containing ceramic green body from the casting apparatus 1311 to a conveyor 1316. In another aspect, as shown, the casting chamber 1309 may be in fluid communication with a solvent reservoir 1305 configured to contain a solvent 1307. In yet another aspect, the solvent 1307 may correspond to one or more solvents in the precursor mixture used to form the solvent-containing ceramic green body. The solvent 1307 in the solvent reservoir 1305 may maintain the casting vapor pressure of the solvent in the environment of the casting chamber 1309. In other respects, the chamber vapor pressure of the solvent in the casting chamber can be configured to fall within one or more corresponding ranges discussed below with reference to the solvent annealing method.

[0130] like Figure 13As shown, the solvent annealing apparatus 1301 includes a solvent loading chamber 1321. In one aspect, as shown, the solvent loading chamber 1321 can be separated from the casting chamber 1309 by a baffle 1306. An orifice 1319 is provided therebetween and configured to allow a solvent-containing ceramic green body 1328 to pass through it, as indicated by arrow 1317. In another aspect, as shown, the solvent annealing apparatus 1301 may optionally include at least one additional source 1315 of solvent 1307, which is shown in another solvent reservoir 1305. If present, the at least one additional source 1315 of solvent 1307 contains the same material as solvent 1307. The at least one additional source 1315 of solvent 1307 may be configured to maintain the chamber vapor pressure of the solvent. Alternatively, the chamber vapor pressure may be maintained by solvent vapor flowing from the casting chamber 1309 (e.g., through the orifice 1319) to the solvent loading chamber 1321. In one aspect, the chamber vapor pressure of the solvent in the solvent loading chamber 1321 is configured to be lower than the casting vapor pressure of the solvent in the casting chamber 1309. In other aspects, the chamber vapor pressure of the solvent in the casting chamber may be configured to fall within one or more corresponding ranges discussed below with reference to the solvent annealing method. In one aspect, as shown, the solvent annealing apparatus 1301 may include one or more heating devices 1323 and / or 1325 configured to heat and / or maintain the chamber temperature of the solvent loading chamber 1321. In other aspects, the chamber temperature of the solvent loading chamber 1321 may be greater than the casting temperature of the casting chamber 1309. In other aspects, the chamber temperature may fall within one or more corresponding ranges discussed below with reference to the solvent annealing method. In other aspects, the temperature encountered by the solvent-containing ceramic green body 1328 transported along the conveyor 1326 in the direction indicated by arrow 1317 may be increased. For example, the first heating device 1323 may be configured to maintain a first temperature below a second temperature, and the second heating device 1325 may be configured to maintain the second temperature. Although two heating devices 1323 and 1325 are shown, it should be understood that in other respects more than two or only one heating device may be provided. Furthermore, the rate at which the conveyor 1316 transports the solvent-containing ceramic green body 1328 through the solvent loading chamber can be configured to fall within one or more corresponding time periods discussed below with reference to the solvent annealing method. Furthermore, it should be understood that in some respects, the solvent loading chamber 1321 may resemble, for example... Figure 5 The device shown and discussed above.

[0131] like Figure 13As shown, the solvent annealing apparatus 1301 includes a drying chamber 1331. In one aspect, as shown, the solvent loading chamber 1321 and the drying chamber 1331 can be separated by a baffle 1324. As shown, the solvent loading chamber 1321 is located between the casting chamber 1309 and the drying chamber 1331. Furthermore, an orifice 1329 is provided to pass through the baffle 1324 and is configured to allow a solvent-containing ceramic green body 1328 to pass through it, as indicated by arrow 1327. In one aspect, the drying vapor pressure of the solvent in the drying chamber 1321 is configured to be lower than the chamber vapor pressure of the solvent in the solvent loading chamber 1321. The drying chamber 1331 includes a distal end 1303 opposite to the baffle 1324, and the drying chamber 1331 also includes a proximal end 1303 adjacent to the baffle 1324 and opposite to the distal end 1303. As indicated by arrow 1327, the solvent-containing ceramic green body 1328 is configured to be transported by conveyor 1316 from the proximal end 1304 to the distal end 1303 of the drying chamber 1331. As discussed below with reference to the partially dried ceramic green body 1338, substantially all the solvent in the solvent-containing ceramic green body 1328 can be removed to become a solvent-free ceramic green body by the time it travels through the outlet 1339 of the solvent annealing apparatus 1301 (as indicated by arrow 1337). In this aspect, as discussed below, the solvent annealing apparatus 1301 can be configured to feed the solvent-free ceramic green body into the processing apparatus 601 (see...). Figure 6 ).

[0132] like Figure 13As shown, the solvent annealing apparatus 1301 includes a ventilation system 1340. The ventilation system 1340 can be configured to circulate an atmosphere from a substantially solvent-free environment through a drying chamber 1331 (e.g., as indicated by arrows 1342, 1346, and / or 1348), thereby removing solvent from the solvent-containing ceramic green body 1328. As shown, the ventilation system 1340 may include multiple orifices (e.g., inlet 1341, air filter 1345, and / or outlet 1347). In one aspect, as shown, the ventilation system 1340 includes an inlet 1341 at a proximal end 1303 of the drying chamber 1331, thereby introducing an atmosphere from a substantially solvent-free environment into the drying chamber 1331, as indicated by arrow 1342. In other aspects, the temperature of the atmosphere introduced through inlet 1341 may include a predetermined temperature, for example, achievable using a heating device 1343. The predetermined temperature may correspond to a drying temperature of the drying chamber 1331, which may be greater than the chamber temperature of the solvent-loaded chamber 1321. In this aspect, the drying temperature may fall within one or more corresponding ranges discussed below with reference to the solvent annealing method. As shown, the ventilation system 1340 includes an outlet at a proximal end 1304 of the drying chamber 1331, configured to remove the atmosphere at the proximal end 1304, as indicated by arrow 1348. Providing an inlet at the distal end of the drying chamber and an outlet at the proximal end enables the atmosphere to flow in the opposite direction to the direction of transport of the solvent-containing ceramic green body 1328 (e.g., arrow 1327), which allows for continuous removal of solvent from the solvent-containing ceramic green body as the atmosphere flows through and / or flows through the drying chamber. Furthermore, providing an outlet at the proximal end of the drying chamber allows for the removal of any solvent from the environment of the solvent-loaded chamber through orifice 1329. In this aspect, as shown, the plurality of orifices also generously include an additional orifice (e.g., air filter 1345) located between the proximal end 1304 and the distal end 1303 (e.g., between outlet 1347 and inlet 1341). In other respects, as shown, the additional orifice (e.g., air filter 1345) can be configured to introduce an additional atmosphere (e.g., a substantially solvent-free environment) into the drying chamber 1331, as indicated by arrow 1346. For example, arrow 1346 shows the introduction of atmosphere into the drying chamber 1331 through air filter 1345, which can reduce particulate matter in the atmosphere that would otherwise be detrimental to the surface quality of the resulting solvent-free ceramic green body and / or sintered article. Although not shown, it is believed that the substantially solvent-free atmosphere introduced through inlet 1341 can also be filtered (e.g., HEPA) and / or may contain low particulate levels (e.g., meeting one or more cleanroom standards for the atmosphere). Introducing the atmosphere at both the distal end and another location (between the distal and proximal ends) can help remove solvent from the solvent-containing ceramic green body at a predetermined rate.

[0133] Now refer to Figure 13The solvent annealing apparatus 1301 shown schematically and Figure 14The partially dried ceramic green body 1338 shown is discussed in relation to aspects of the solvent annealing method. The method may include casting a precursor solution in a casting chamber 1309 to form a solvent-containing ceramic green body 1328. In this aspect, the precursor solution may include compositions within one or more of the ranges discussed above. In this aspect, casting may correspond to step 711 discussed above and / or may include any one or more aspects discussed above (e.g., composition, thickness). In this aspect, the casting chamber 1309 may include a solvent casting vapor pressure corresponding to the solvent in the solvent-containing ceramic green body 1328. In other respects, the casting vapor pressure may be: about 100 Pascals or greater, about 500 Pascals or greater, about 1,000 Pascals or greater, about 5,000 Pascals or greater, about 10,000 Pascals or greater, about 20,000 Pascals or greater, about 30,000 Pascals or greater, about 40,000 Pascals or greater, about 50,000 Pascals or greater, about 60,000 Pascals or greater, or differ from the vapor pressure of the solvent at its boiling point by a range of 10,000 Pascals. In other respects, the casting vapor pressure can be in the range of about 100 Pascals to about 50,000 Pascals, about 500 Pascals to about 50,000 Pascals, about 1,000 Pascals to about 50,000 Pascals, about 5,000 Pascals to about 40,000 Pascals, about 10,000 Pascals to about 30,000 Pascals, about 20,000 Pascals to about 30,000 Pascals, or all ranges or subranges thereof. As discussed above, the casting vapor pressure can be maintained and / or supplied by solvent 1307 from solvent reservoir 1305 in fluid communication with casting chamber 1309. Solvent reservoir 1305 can be maintained at a reservoir temperature greater than the casting temperature of casting chamber 1309, which can facilitate solvent evaporation from solvent reservoir. For example, the reservoir temperature can be: about 50°C or higher, about 60°C or higher, about 65°C or higher, about 70°C or higher, about 75°C or higher, about 80°C or higher, about 95°C or lower, about 90°C or lower, about 85°C or lower, or about 80°C or lower. In another aspect, the reservoir temperature can be a range of about 50°C to about 95°C, about 55°C to about 90°C, about 60°C to about 85°C, about 65°C to about 80°C, about 70°C to about 80°C, or any range or subrange thereof. In another aspect, the casting vapor pressure can correspond to the vapor pressure of one or more of propylene glycol, methyl ethyl ketone, dimethyl carbonate, toluene, or combinations thereof. In other aspects, the casting vapor pressure can correspond to the vapor pressure of a single solvent, and the solvent can be the same as the solvent in the composition of the solvent-containing ceramic green body 1328.Providing a casting vapor pressure (e.g., about 100 Pascals or more, about 1,000 Pascals to about 50,000 Pascals) can limit the amount of solvent evaporation from the solvent-containing ceramic green body during the casting process and / or in the casting chamber, which is related to the good surface quality of the resulting solvent-free ceramic green body and / or sintered product.

[0134] After casting the solvent-containing ceramic green body 1328 (e.g., in casting chamber 1309), as Figure 13 As shown, the solvent-containing ceramic green body 1328 can be transported to the solvent loading chamber 1321 for solvent annealing, for example, by conveyor 1316 through orifice 1319 (as indicated by arrow 1317). In one aspect, solvent annealing in the solvent loading chamber 1321 can correspond to step 713 discussed above. In another aspect, the chamber vapor pressure of the solvent in the solvent loading chamber 1321 can be less than the casting vapor pressure of the solvent in the casting chamber 1309. In other aspects, the chamber vapor pressure can be maintained by one or more of the following: an atmosphere containing the casting vapor pressure entering the solvent loading chamber 1321 (e.g., through orifice 1319); solvent evaporation from an additional source 1315 of optional solvent 1307; a controlled rate at which the solvent leaves the solvent-containing ceramic green body 1328; and combinations thereof. In other respects, the additional source 1315 of solvent 1307 may not be maintained at a separate temperature (different from solvent reservoir 1305), and / or the additional source 1315 of solvent 1307 may include one or more containers (e.g., dishes) for condensation and re-evaporation of solvent 1307 in solvent loading chamber 1321.

[0135] In other respects, the chamber vapor pressure can be: about 20 Pascals or higher, about 50 Pascals or higher, about 100 Pascals or higher, about 500 Pascals or higher, about 1,000 Pascals or higher, about 5,000 Pascals or higher, about 10,000 Pascals or higher, about 20,000 Pascals or higher, about 50,000 Pascals or lower, about 40,000 Pascals or lower, about 30,000 Pascals or lower, about 20,000 Pascals or lower, about 10,000 Pascals or lower, or about 8,000 Pascals or lower. In other respects, the chamber vapor pressure can be in the range of about 20 Pascals to about 50,000 Pascals, about 50 Pascals to about 50,000 Pascals, 100 Pascals to about 50,000 Pascals, about 500 Pascals to about 50,000 Pascals, about 1,000 Pascals to about 50,000 Pascals, about 5,000 Pascals to about 40,000 Pascals, about 10,000 Pascals to about 30,000 Pascals, about 20,000 Pascals to about 30,000 Pascals, or all ranges or subranges thereof. Providing a chamber vapor pressure (e.g., about 20 Pascals or greater, about 1,000 Pascals to about 50,000 Pascals, and / or less than the casting vapor pressure) can facilitate the controlled removal of solvents from solvent-containing ceramic green bodies.

[0136] In one aspect, the temperature of the solvent-loading chamber 1321 can be greater than the casting temperature of the casting chamber 1309. In other aspects, the temperature of the solvent-loading chamber 1321 can be: about 40°C or higher, about 50°C or higher, about 60°C or higher, about 65°C or higher, about 70°C or higher, for example, the following ranges: about 40°C to about 100°C, about 50°C to about 90°C, about 60°C to about 80°C, or any range or subrange thereof. Figure 13As shown, one or more heating devices 1323 and / or 1325 can heat the solvent-loaded chamber 1321 and / or the solvent-containing ceramic green body 1328 transported therethrough. In other aspects, the one or more heating devices 1323 and / or 1325 can generate multiple heating zones 132d and / or temperature gradients in the solvent-loaded chamber 1321, such that the temperature encountered by the solvent-containing ceramic green body 1328 increases as it is transported through the solvent-loaded chamber 1321 (e.g., in the direction indicated by arrow 1317). Providing the solvent-containing ceramic green body with the temperature rise encountered during transport through the solvent-loaded ceramic green body can facilitate controlled and continuous removal of solvent from the solvent-loaded ceramic green body as part of a solvent annealing process. In this aspect, the time spent by the solvent-containing ceramic green body 1328 in the solvent loading chamber 1321 (e.g., the heating time in the solvent loading chamber) can be: about 3 minutes or longer, about 4 minutes or longer, about 5 minutes or longer, about 6 minutes or longer, about 8 minutes or longer, about 10 minutes or longer, about 30 minutes or less, about 20 minutes or less, about 10 minutes or less, about 9 minutes or less, about 8 minutes or less, about 7 minutes or less, about 6 minutes or less, or about 5 minutes or less. In this aspect, the time spent by the solvent-containing ceramic green body 1328 in the solvent loading chamber 1321 (e.g., the heating time in the solvent loading chamber) can be within the following ranges: about 3 minutes to about 30 minutes, about 3 minutes to about 20 minutes, about 3 minutes to about 10 minutes, about 4 minutes to about 9 minutes, about 5 minutes to about 8 minutes, about 6 minutes to about 7 minutes, or any range or subrange thereof.

[0137] In this respect, after the solvent-containing ceramic green body 1328 is transported through the solvent loading chamber 1321, as... Figure 13As shown, the method may include transporting a solvent-containing ceramic green body 1328 to a drying chamber 1331, for example, via an orifice 1329 (as indicated by arrow 1327) on a conveyor 1316. In other aspects, the drying vapor pressure of the solvent in the drying chamber 1331 may be less than the chamber vapor pressure and the casting vapor pressure. In other aspects, the drying vapor pressure may be: about 20 Pascals or less, about 15 Pascals or less, about 10 Pascals or less, about 5 Pascals or less, or about 1 Pascal or less. Providing a drying vapor pressure of about 20 Pascals or less can facilitate the removal of the solvent from the solvent-containing ceramic green body to form a solvent-free ceramic green body. In other aspects, the drying chamber 1331 may be maintained at a drying temperature greater than the casting temperature and the chamber temperature. In other aspects, the drying temperature may differ from the boiling point of the solvent by about 20°C, about 15°C, or about 10°C. In other respects, the room temperature may be: about 70°C or higher, about 75°C or higher, about 80°C or higher, about 85°C or higher, about 90°C or higher, about 130°C or lower, about 110°C or lower, about 100°C or lower, or about 90°C or lower. In other respects, the room temperature may be a range of about 70°C to about 130°C, about 75°C to about 110°C, about 80°C to about 100°C, about 85°C to about 90°C, or any range or subrange thereof. In other respects, such as Figure 13 As shown, the drying temperature can be maintained by heating the atmosphere and / or the solvent-containing ceramic green body in the drying chamber using heating device 1343. In other aspects, heating can be performed by heating the atmosphere introduced into the drying chamber 1331 from a substantially solvent-free environment by causing the atmosphere to flow around the heating device 1343 (e.g., placed in inlet 1341), but in other aspects, the location of the heating device can be other locations.

[0138] In this regard, such as Figure 13As shown, drying the solvent-containing ceramic green body may include introducing an atmosphere from a substantially solvent-free environment into the drying chamber 1331. In other aspects, as shown, the atmosphere may be introduced through inlet 1341 (as indicated by arrow 1342), which may be located at the distal end 1303 of the drying chamber. Furthermore, as shown, the atmosphere may be removed from the drying chamber through outlet 1347 located at the proximal end 1304 of the drying chamber 1331 (as indicated by arrow 1348). Providing an inlet at the distal end and an outlet at the proximal end of the drying chamber enables the atmosphere to flow in the opposite direction to the transport direction of the solvent-containing ceramic green body 1328 (e.g., arrow 1327), which allows for continuous removal of solvent from the solvent-containing ceramic green body as the atmosphere flows through and / or flows through the drying chamber. Furthermore, providing an outlet at the proximal end of the drying chamber allows for the removal of any solvent from the environment of the solvent-loading chamber through orifice 1329. In other respects, an atmosphere can be introduced from a substantially solvent-free environment at multiple locations, including at inlet 1341 at the distal end 1303 and at additional locations between the distal end 1303 and the proximal end 1304 and / or between inlet 1341 and outlet 1347 (e.g., air filter 1345, as indicated by arrow 1346). Introducing an atmosphere at both the distal end and the other location (between the distal and proximal ends) can facilitate the removal of solvent from the solvent-containing ceramic green body at a predetermined rate. In other respects, the average velocity of the atmosphere above the solvent-containing ceramic green body in the drying chamber 1331 (e.g., measured at position 1351) may be: about 0.1 m / s, about 0.08 m / s, about 0.05 m / s, about 0.03 m / s, about 0.02 m / s, about 0.01 m / s, or about 0.01 m / s or greater, for example, the following ranges: about 0.01 m / s to about 0.1 m / s, about 0.01 m / s to about 0.08 m / s, about 0.01 m / s to about 0.05 m / s, about 0.01 m / s to about 0.03 m / s, about 0.01 m / s to about 0.02 m / s, or any range or subrange thereof. Providing an atmosphere with a low average velocity (e.g., about 0.1 m / s or less, or about 0.01 m / s to about 0.1 m / s) above the solvent-containing ceramic green body can contribute to uniform drying and / or good surface quality of the resulting solvent-free ceramic green body and / or the resulting sintered article. The average velocity of the atmosphere above the solvent-containing ceramic green body can be lower than the average velocity of the atmosphere at other locations in the drying chamber (e.g., location 1353 near the additional atmosphere source between the far end 1303 and the near end 1304, or location 1355 near the outlet 1347 at the near end 1304), which can contribute to high surface quality of the resulting article while exchanging a larger volume of atmosphere through the drying chamber 1331 to maintain a low chamber vapor pressure.

[0139] Figure 14 Display drying chamber 1331 (see also) Figure 13 The first main surface 1333 of the partially dried ceramic green body 1338 includes a solvent-containing portion 1401 and a solvent-free portion 1421, with a boundary 1406 between them. As shown, the boundary 1406 varies between extremes 1408a, 1408b, and 1408c at a solvent-free threshold 1409 and opposite extremes 1404a and 1404b at a solvent-containing threshold 1403, which is located downstream of the solvent-containing threshold 1403, as indicated by arrow 1327. As shown, the partially dried ceramic green body 1338 may include a dried portion 1407 comprising two regions between the solvent-free threshold 1409 and the solvent-containing threshold 1403. The position of the solvent-free threshold 1409, the solvent-containing threshold 1403, and the distance between them can be controlled by the drying vapor pressure, the drying temperature, and the average velocity of the atmosphere above the solvent-containing ceramic green body. When a solvent-containing ceramic green body dries too quickly, surface defects can form in the resulting solvent-free ceramic green body. This can be caused, for example, by drying a surface section before the surrounding portion of the ceramic green body, which can lead to the separation of that section from the main body of the ceramic green body.

[0140] Example

[0141] The various aspects are further illustrated by the following examples. Examples 1-14 and Comparative Example AA-CC were analyzed by TGA and DSC as described above. Examples 1-3 and Comparative Example AA are polymers without alkali metal-containing ceramic particles. Examples 4-14 and Comparative Example BB-CC are ceramic green bodies containing lithium cobalt oxide (LCO) particles with a median particle size of 0.45 μm as alkali metal-containing ceramic particles. In Examples 1, 4, 6-7, and 11, the polymer is poly(butylene carbonate) (PBC). In Examples 2, 5, 9, and 12-13, the polymer is poly(propylene carbonate) (PPC). In Example 3, the polymer is a linear random copolymer, namely poly(propylene-co-cyclohexylene carbonate) (PPCC). In Example 10, the polymer is 50 wt% PBC and 50 wt% PPC. In Example 14, the polymer is a combination of PBC and PPC (see Table 3). In Comparative Example AA-BB, the polymer is poly(vinyl butyral) (PVB). In Comparative Example CC, the polymer is a blend of 95% by weight PBC and 5% by weight poly(methyl methacrylate) (PMMA) (PBC / PMMA). As used in the examples, the molecular weight Mn of PVB is 100,000 Da, the molecular weight Mn of PPC is 120,000 Da, the molecular weight Mn of PBC is 200,000 Da, and the molecular weight of PPCC is 250,000 Da.

[0142] Figure 8 And 10-11 shows the TGA quality loss curve. In Figure 8 and 10 In -11, the horizontal axis 801, 1001, or 1101 represents temperature (in °C). Figure 8 In the diagram, the vertical axis 803 represents the fraction of the remaining original mass. Figure 8 In the diagram, curves 805, 807, 809, 811, 813, and 815 are mass loss curves, showing the fraction of the original mass remaining at a given temperature, and corresponding to Examples 1-2 and 4-7, respectively. Figure 10-11 In the figure, the vertical axis 1003 or 1103 represents the percentage of the remaining original mass. Figure 10 In the figure, curves 1005 and 1007 are mass loss curves, showing the percentage of the original mass remaining at a given temperature, and corresponding to Example 3 and Comparative Example AA, respectively. Figure 11 In the figure, curves 1105, 1107, 1109 and 1111 are mass loss curves, showing the percentage of the original mass remaining at a given temperature and corresponding to Comparative Example BB, Comparative Example CC, Example 8 and Example 10, respectively.

[0143] Figure 9 and 12 This displays the heat flow from the DSC. Figure 9 and 12 In the diagram, the horizontal axis 901 or 1201 represents temperature (in °C), and the vertical axis 903 or 1203 represents heat flux (in W / g), with positive values ​​corresponding to exothermic heat flux (i.e., heat emitted from the sample). Figure 9 In this context, heat is measured per mass of ceramic green body; however, in... Figure 12 In this context, heat flux is the polymer per mass of ceramic green body. Figure 9 In the diagram, curves 905, 907, 909, 911, 913, and 915 are heat flow curves, showing the heat flow from the sample at a given temperature, and corresponding to Examples 1-2 and 4-7, respectively. Figure 12 In the figure, curves 1205, 1207, 1209 and 1211 are heat flow curves, showing the heat flow from the sample at a given temperature and corresponding to Comparative Example BB, Example 8, Comparative Example CC and Example 10, respectively.

[0144] Figure 10The mass loss curves for Example 3 (PPCC) and Comparative Example A (PVB) are shown. Curve 1007 shows that Comparative Example A experienced mass loss in several different processes based on slope changes at approximately 150°C, approximately 200°C, approximately 350°C, and from 400°C to 500°C. Furthermore, curve 1007 suggests that PVB cannot be completely removed from the ceramic green body up to 500°C or higher. Conversely, curve 1005 suggests that at temperatures below 350°C, virtually all of the PPCC (Example 3) is removed from the ceramic green body. Moreover, curve 1005 shows a more uniform loss of mass between 50°C and 250°C compared to curve 1007. Figure 8 In the figure, curves 805 and 807 are the mass loss curves of Examples 1 and 2, respectively. Curves 805 and 807 suggest that at temperatures below 300°C, virtually all PBC (Example 1) and PPC (Example 2) will be removed.

[0145] exist Figure 9 In the figures, curves 905 and 907 show the heat flow profiles for Examples 1-2. Curves 905 and 907 show a significant endothermic (negative heat flow) from about 200°C to about 300°C. The endothermic heating behavior (i.e., heat absorbed by the sample) of Examples 1-2 indicates that PBC and PPC undergo depolymerization rather than chain scission. As discussed above, it is believed that carbonate-based polymers and acrylate-based polymers (e.g., methacrylate-based polymers) decompose via depolymerization. The endothermic depolymerization of PBC and PPC suggests that they reduce the likelihood of runaway heating because depolymerization absorbs rather than releases heat, which allows for an increase in heating rate without affecting the quality of the resulting sintered article.

[0146] Table 2 presents the compositions of Examples 4-10 and Comparative Example BB-CC. Dibutyl phthalate (DBP) and polyethylene glycol 400 (PEG) are viscosity modifiers. KD1 and KD73 are Hypermer dispersants (purchased from Croda Energy Technologies). Fish oil is a dispersant. Dibutyl maleate (DBM) is a plasticizer. Unless otherwise stated, the LCO particles were heated at 150°C for 2 hours before being mixed with the other components in Table 2. For Examples 6-7, the LCO particles were heated at 900°C in water-loaded air for 5 minutes or 10 minutes, respectively, as described below. Figure 8-9 As discussed, the ceramic green body was cast using a surgical scraper, wherein a precursor solution containing the compositions in Table 2 was mixed with a solvent, wherein the compositions in Table 2 represent approximately 60% by weight of the precursor solution.

[0147] Table 2: Composition (wt%) of Examples (Ex) 4-10 and Comparative Example (CE) BB-CC

[0148]

[0149]

[0150] Figure 11 The mass loss curves for Comparative Example BB, Comparative Example CC, Example 8, and Example 10 are shown. Curve 1105 is the mass loss curve for Comparative Example BB, which shows a lower mass loss at a higher temperature compared to curve 1007 (e.g., about 75°C lower), suggesting that the alkali metal-containing ceramic particles (LCO) catalyze the decomposition of PVB. Similarly, curve 1107 shows mass loss occurring at a lower temperature. For example, curves 1107, 1109, and 1111 (Examples 8, 10, and Comparative Example CC) have similar shapes and indicate that more than 70%, more than 80%, or more than 90% (e.g., substantially all) of the organic material is removed before 300°C.

[0151] Figure 12 The heat flow profiles of Comparative Example BB, Comparative Example CC, Example 8, and Example 10 are shown. Figure 12 The heat flux in the figure is the polymer contained per mass of ceramic green body. Curves 1205, 1207, 1209, and 1211 show the exothermic heat flux within the indicated temperature range. Curve 1209 (Comparative Example CC) shows the largest exothermic heat flux (e.g., greater than 3 W / g). Compared to curve 1211 (Example 10), curve 1209 (Comparative Example CC) has a larger maximum heat flux, and this maximum value occurs at a higher temperature. This confirms that even the addition of 5 wt% PMMA to Comparative Example CC significantly increases the maximum heat flux. Although methacrylate-based polymers have the ability to decompose through depolymerization, Figure 12 It was confirmed that PMMA (a methacrylate-based polymer) undergoes exothermic decomposition (e.g., through chain scission), which significantly increases the maximum heat flux and the risk of runaway decomposition, flammability, and / or surface defects when heating ceramic green bodies (compared to Example 10). Figure 12 As shown, curve 1209 (Comparative Example CC) includes a maximum heat flux exceeding 3 W / g, and curve 1205 (Comparative Example BB) includes a maximum heat flux of about 3 W / g, while curves 1207 and 1211 (Examples 8 and 10) include a maximum heat flux of about 2.5 W / g or less. The lower maximum heat flux of Examples 8 and 10 may enable faster processing (e.g., heating) of the ceramic green body while maintaining high-quality sintered products, such as with a lower risk of runaway decomposition, flammability, and / or surface defects. Curves 1207 and 1211 (Examples 8 and 10) have the lowest heat flux, and curve 1207 (Example 8) has the lowest maximum heat flux. Figure 12 The curve shown has its maximum heat flux at its lowest temperature.

[0152] Figure 8 Curves 809 and 811 in the figure correspond to the mass loss curves of Examples 4-5, respectively. (See above for reference.) Figure 11 It is noted that the alkali metal-containing ceramic particles (LCO) reduce the temperature at which the maximum mass loss occurs, for example, from about 250°C to about 275°C in curves 805 and 807 to about 200°C in curves 809 and 811 (e.g., about 75°C lower). Figure 9 Curves 909 and 911 in the figure correspond to the heat flow curves of Examples 4-5, respectively. Unlike... Figure 12 In the situation, Figure 9 The heat flux recorded is per mass of the entire ceramic green body. As shown, curves 909 and 911 are exothermic, with a maximum heat flux of approximately 230°C. Compared to curves 905 and 907, curves 909 and 911 reach their extreme values ​​at lower temperatures (e.g., 235°C vs. approximately 245°C to approximately 250°C) and are exothermic (rather than endothermic). The exothermic heat flux is attributed to the alkali metal-containing ceramic particles catalyzing more chain scission (exothermic) (compared to what is observed in homopolymers). Curve 909 (Example 4; PBC) has a lower maximum heat flux than curve 911 (Example 5; PPC), although... Figure 8 The corresponding mass loss curves 809 and 811 appear to be essentially the same. (As mentioned above...) Figure 12 As demonstrated in the study, the PBC polymer (curve 1211) has a lower maximum heat flux compared to acrylate-containing polymers (PBC / PMMA; curve 1209) and PVB polymers (curve 1205).

[0153] For Examples 6-7, the LCO particles were heated at 900°C for 5 or 10 minutes, respectively, instead of at 150°C for 2 hours as in Examples 4-5. It is believed that the high-temperature treatment in Examples 6-7 reduced the surface concentration of alkali metals on the LCO particles because some alkali metals volatilized during the treatment. Figure 8 As shown, curves 813 and 815 (Examples 6-7) are compared to Figure 8 Any other curve in the curve loses mass at lower temperatures. However, as... Figure 9As shown, curves 913 and 915 (Examples 6-7) exhibit an endothermic peak heat flux of approximately -0.5 W / g at approximately 180°C to approximately 190°C, followed by a maximum exothermic heat flux of approximately 1 W / g or less at approximately 260°C to approximately 270°C. Compared to curves 909 and 911, the heat flux of curves 913 and 915 is reduced by nearly an order of magnitude. The endothermic peaks of curves 913 and 915 are associated with depolymerization. It is believed that alkaline lithium-containing compounds with reduced, but not non-zero, LCO particles (treated at 900°C in Examples 6-7, compared to 150°C in Examples 4-5) can catalyze depolymerization at lower temperatures rather than chain scission. The low exothermic peaks of 913 and 915 indicate a significantly reduced risk for heating ceramic green bodies.

[0154] Table 3 shows the compositions that can be used to obtain defect-free fired belts and the maximum firing speed. The heating equipment includes: a first oven with a length of 50 cm, multi-zoned at a set temperature, which rises approximately linearly along its length from about 100°C to a maximum temperature of about 280°C; and a second oven connected to it with a length of approximately 500 cm, which operates along its length at temperatures from about 1000°C to about 1300°C. Samples of Examples 11-14, comprising a length of 12 cm and a width of 3.5 cm, and Comparative Example BB, were placed on an alumina substrate and passed through the oven at a predetermined speed via a stack of air bearings. Predetermined speeds of 2.1 mm / s, 4.2 mm / s, 6.3 mm / s, 8.4 mm / s, 12.6 mm / s, 16.8 mm / s, and 21.0 mm / s were tested. Example 11 has the same composition as Example 4. In Table 3, PC refers to propylene carbonate, which is used as a plasticizer. Example 14 uses LCO particles that have been heated in water-loaded air at 900°C for 5 minutes.

[0155] As shown in Table 3, Comparative Example BB achieved a maximum speed of 2.1 mm / s. At higher speeds, Comparative Example BB burned between the first and second ovens. Examples 11-14 achieved speeds greater than 5 mm / s and greater than 8 mm / s. Example 13 achieved a maximum speed of 8.4 mm / s. Furthermore, Examples 11-12 and 14 achieved speeds greater than 10 mm / s and 12 mm / s (corresponding to processing times of 1 minute or less or about 40 seconds or less in the first oven). Examples 11-12 achieved a maximum speed of 12.6 mm / s. Example 14 operated at a maximum speed of 21 mm / s (corresponding to a processing time of 24 seconds in the first oven), which is 10 times faster than the maximum speed of Comparative Example BB. Examples 11-14 demonstrate that using carbonate-based polymers can achieve faster processing while producing high-quality sintered articles. Furthermore, combinations of carbonate-based polymers and / or plasticizers can further increase processing rates. Considering the removal of a higher organic content (e.g., 3-4 times more organic matter), it is unexpected that faster speeds can be achieved using Examples 11-14 (compared to Comparative Example BB).

[0156] Table 3: Composition (wt%) and maximum speed of Examples (Ex) 11-14 and Comparative Example (CE) BB

[0157]

[0158] Build something like Figure 13 The solvent annealing apparatus 1301 shown is a solvent annealing apparatus, and the average velocity of the atmosphere at positions 1351, 1353, and 1355, as well as in the solvent loading chamber, is measured. The average velocity of the atmosphere in the solvent loading chamber is less than 0.1 m / s. The average velocity of the atmosphere at position 1351 (i.e., the atmosphere flowing above the solvent-containing ceramic green body in the drying chamber) is also less than 0.1 m / s. The average velocity of the atmosphere at position 1353 (i.e., near the additional inlet between the proximal and distal ends) is approximately 0.7 m / s. The average velocity of the atmosphere at position 1355 (i.e., near the outlet) is approximately 1 m / s. Therefore, the solvent loading apparatus can provide a lower average atmosphere velocity above the solvent-containing ceramic green body compared to the average velocity at other positions in the drying chamber. Examples of the solvent annealing apparatus with the compositions of Examples 4-10 were produced using this apparatus, and high-quality solvent-free ceramic green bodies were obtained.

[0159] The above observations can be combined to provide ceramic green bodies comprising carbonate-based polymers, sintered articles formed from the ceramic green bodies, and methods for manufacturing the same. Providing carbonate-based polymers allows for faster processing of the resulting ceramic green bodies to form sintered articles, for example, by reducing the occurrence of events that could compromise the quality of the sintered articles during the heating of the green body. For example, carbonate-based polymers can provide reduced flammability during the heating of the ceramic green body. Flammability is associated with larger molecular weights (e.g., 200 Daltons or greater) corresponding to the bonding of multiple monomers, which can result in, for example, chain scission during heating. It is not desirable to be limited by theory that carbonate-based polymers and acrylate-based polymers (e.g., methacrylate-based polymers) decompose via depolymerization in addition to chain scission, while other polymers decompose only via chain scission. However, as demonstrated in the examples above, in the presence of alkali metal-containing ceramic particles, it was unexpectedly found that methacrylate-based polymers decompose primarily via chain scission, while carbonate-based polymers decompose primarily via depolymerization. It is undesirable to be limited by theory that alkali metal-containing ceramic particles will cause debonding problems (i.e., removal of the organic components of the green body) within a short period of time (e.g., about 4 minutes or less) because alkali metals catalyze the chain scission of flammable components (e.g., polymers) in the binder system, which can damage the ceramic and / or the resulting sintered product. Providing reduced heat flux (e.g., about 7 W / g ceramic green body or less, about 2 W / g polymer in the ceramic green body) can reduce the probability of introducing defects during heating, such as flammability from runaway thermal decomposition or polymer decomposition, and / or enable faster processing of ceramic green bodies while maintaining high-quality sintered products.

[0160] Heating the alkali metal-containing ceramic particles prior to mixing and / or casting the ceramic green body can cause the material adsorbed onto the alkali metal-containing ceramic particles to volatilize and / or reduce the amount of alkali metal on the surface of the alkali metal-containing ceramic particles. Mixing the alkali metal-containing ceramic particles with a solvent and optionally a dispersant (e.g., without additional materials) can provide good dispersion of the alkali metal-containing ceramic particles in the solvent (with little or no agglomerates), which can improve the dispersion and / or distribution of the alkali metal-containing ceramic particles during subsequent steps of the process. As discussed above, providing a dispersant can improve the dispersion and / or distribution of the alkali metal-containing ceramic particles, and / or can increase the time during which the dispersion of the alkali metal-containing ceramic particles can be maintained. Carbonate-based polymers can achieve increased processing speeds (e.g., faster debinding of the resulting ceramic green body) and / or increased quality of the resulting sintered article. Providing a viscosity modifier can achieve a second mixture with a predetermined viscosity, which can enable casting of the ceramic green body while achieving dimensional stability of the ceramic green body. Providing a reduced-pressure environment containing solvent can reduce solvent loss in the second mixture during degassing to form the precursor mixture. Providing a reduced-pressure environment can reduce dissolved gases in the second mixture, thereby providing a precursor mixture that can form a ceramic green body with a uniform, high-quality surface. Solvent annealing can produce a higher-quality ceramic green body with reduced defects, which can be used to form a higher-quality sintered product with fewer defects compared to what would be obtained without solvent annealing. In this aspect, the first oven 603 and the second oven 605 can be connected to each other and / or adjacent to each other, so that the temperature of the debonded ceramic product 611 does not drop significantly (e.g., about 100°C or less, about 50°C or less), which can reduce energy costs, processing time, and / or processing space requirements.

[0161] This disclosure also provides a solvent annealing apparatus including a solvent loading chamber configured to control the solvent removal rate of a solvent-containing ceramic green body. Solvent annealing can produce higher quality ceramic green bodies with reduced defects, which can be used to form higher quality sintered articles with fewer defects compared to those obtained without solvent annealing. The casting vapor pressure of the solvent provided in the casting chamber (e.g., about 100 Pascals or greater, about 1000 Pascals to about 50000 Pascals, and / or within 10000 Pascals of the boiling point vapor pressure of the solvent) can limit the amount of solvent evaporating from the solvent-containing ceramic green body during casting and / or in the casting chamber, which is related to the good surface quality of the resulting solvent-free ceramic green body and / or sintered article. Providing a chamber vapor pressure (e.g., about 20 Pascals or greater, about 1000 Pascals to about 50000 Pascals, and / or less than the casting vapor pressure) for the solvent in the solvent-loaded chamber can facilitate controlled removal of the solvent from the solvent-containing ceramic green body. Providing the solvent-containing ceramic green body with the temperature rise encountered during transport through the solvent-loaded ceramic green body can promote controlled and continuous removal of the solvent from the solvent-loaded ceramic green body as part of a solvent annealing process. Providing a drying vapor pressure of about 20 Pascals or less in the drying chamber can facilitate solvent removal from the solvent-containing ceramic green body to form a solvent-free ceramic green body. Providing an inlet at the distal end and an outlet at the proximal end of the drying chamber enables the atmosphere to flow in the opposite direction to the transport direction of the solvent-containing ceramic green body, which allows for continuous removal of the solvent from the solvent-containing ceramic green body as the atmosphere flows through and / or through the drying chamber. Furthermore, providing an outlet at the near end of the drying chamber allows for the removal of any solvent from the environment of the solvent-loaded chamber through orifice 1329. Introducing an atmosphere at both the far end and another location (between the far and near ends) can facilitate the removal of solvent from the solvent-containing ceramic green body at a predetermined rate. Providing an atmosphere with a low average velocity (e.g., about 0.1 m / s or less, or about 0.01 m / s to about 0.1 m / s) above the solvent-containing ceramic green body can contribute to uniform drying and / or a good surface quality of the resulting solvent-free ceramic green body and / or the resulting sintered article. The average velocity of the atmosphere above the solvent-containing ceramic green body can be lower than the average velocity of the atmosphere at other locations in the drying chamber, which can contribute to a high surface quality of the resulting article while allowing a larger volume of atmosphere exchange through the drying chamber 1331 to maintain a low chamber vapor pressure.

[0162] The directional terms used in this article, such as up, down, left, right, front, back, top, and bottom, are only for reference to the accompanying drawings and are not intended to indicate absolute orientation.

[0163] It will be understood that the various aspects revealed may relate to specific features, elements, or steps described together with a particular aspect. It will also be understood that while a specific feature, element, or step may be described in conjunction with an aspect, different aspects may be interchanged or combined with each other in various combinations or transformations not shown.

[0164] It should also be understood that the terms “the,” “an,” or “a” as used herein mean “at least one (a)” and should not be limited to “only one (a)” unless explicitly stated otherwise. Thus, for example, a “a” component includes aspects having two or more such components, unless otherwise explicitly stated in the text. Similarly, “multiple” is intended to mean “more than one.”

[0165] As used herein, the term “about” indicates that a quantity, size, formulation, parameter, and other variable and characteristic is not, and does not need to be, exact, but may be approximate and / or larger or smaller as required, reflecting tolerances, conversion factors, rounding and measurement errors, and other factors known to those skilled in the art. In this document, a range may be expressed as beginning “about” another specific value and / or ending “about” another specific value. When such a range is expressed, an aspect includes beginning with one specific value and / or ending with another specific value. Similarly, when the antecedent “about” is used to indicate that a numerical value is an approximation, it should be understood that a specific numerical value constitutes another aspect. Whether or not the endpoints of a numerical value or range in this specification are stated as “about,” the endpoints of that numerical value or range are intended to include both aspects: one modified by “about” and one not modified by “about.” It should also be understood that the endpoint values ​​of each range are meaningful both in relation to and unrelated to another endpoint value.

[0166] The terms “basically,” “substantially,” and their variations, as used herein, are intended to indicate that the described feature is equivalent to or approximately identical to a numerical value or description. For example, a “substantially flat” surface is intended to indicate a flat or approximately flat surface. Furthermore, as defined above, “substantially similar” is intended to indicate that two values ​​are equal or approximately equal. In an aspect, “substantially similar” can mean that numerical values ​​differ from each other by approximately 10%, for example, by approximately 5%, or by approximately 2%.

[0167] Unless otherwise stated, it is not intended to be construed as requiring the steps of any method described herein to be performed in a specific order. Therefore, when a method claim does not actually state that its steps follow a certain order, or does not specifically indicate in the claims or description that the steps are limited to a specific order, it is not intended to imply any particular order.

[0168] While the transitional phrase "comprising" is used to disclose various features, elements, or steps of a particular aspect, it should be understood that this implies alternative aspects that may be described using transitional phrases such as "consisting of" or "essentially composed of." Thus, for example, the implied alternative aspects of a device comprising A+B+C include aspects where the device is composed of A+B+C and aspects where the device is primarily composed of A+B+C. As used herein, unless otherwise stated, the terms "comprising" and "including," and their variations, should be understood as synonyms and open-ended.

[0169] The features of the foregoing and those aspects are exemplary and may be provided individually or in any combination of any one or more features of other aspects provided herein without departing from the scope of this disclosure.

[0170] It will be apparent to those skilled in the art that various modifications and variations can be made to this disclosure without departing from its scope and spirit. Therefore, this disclosure covers modifications and variations thereof, provided they fall within the scope of the appended claims and their equivalents.

Claims

1. A ceramic green body, comprising, in terms of weight percent of the ceramic green body without a solvent: from about 5 wt % to about 20 wt % of a carbonate-based polymer; about 70% to about 95% by weight of ceramic particles containing an alkali metal; 0% to about 5% by weight of a dispersant; and 0 wt % to about 5 wt % of a viscosity modifier.

2. The ceramic green body according to claim 1, wherein The alkali metal-containing ceramic particles are lithium-containing ceramic particles.

3. The ceramic green body according to any one of claims 1 to 2, wherein: Carbonate-based polymers are composed of alkyl carbonate esters.

4. The ceramic green body according to any one of claims 1 to 3, wherein: Viscosity modifiers include dibutyl carboxylate.

5. The ceramic green body according to any one of claims 1 to 3, wherein: Viscosity modifiers include: dibutyl phthalate, dibutyl adipate, dibutyl maleate, poly(ethylene glycol), or combinations thereof.

6. The ceramic green body according to any one of claims 1 to 5, wherein: The alkali metal-containing ceramic particles have a median particle size of about 0.5 microns or less.

7. The ceramic green body according to any one of claims 1 to 6, wherein: The ratio of the weight of the ceramic green body without solvent to the weight of the ceramic green body with solvent is from about 0.5 to about 0.

7.

8. A method for forming a sintered product: heating the ceramic green body at a maximum temperature of about 300° C. or less for a first period of time of about 4 minutes or less, the heating removing about 70% by weight or more of the organic material in the ceramic green body; and then sintering the ceramic green body at a second temperature of about 700° C. to about 1500° C. for a second time period of about 30 minutes to about 5 hours to form a sintered article comprising a relative density of about 90% or greater of a theoretical density, in, The ceramic green body comprises a carbonate-based polymer and alkali metal-containing ceramic particles.

9. The method of claim 8, wherein: The heating removes about 90% or more of the organic material in the ceramic green body.

10. The method according to any one of claims 8 to 9, wherein: The maximum temperature is about 260° C. or less, and the first time period is about 1 minute or less.

11. The method according to any one of claims 8 to 10, wherein: The maximum heat flow from the ceramic green body during heating, measured in watts per gram of polymer in the ceramic green body (W / g), is about 2 W / g or less.

12. The method according to any one of claims 8 to 11, wherein: The ceramic green body comprises, in weight percent of the ceramic green body without solvent: from about 5 wt % to about 20 wt % of a carbonate-based polymer; about 70% to about 95% by weight of ceramic particles containing an alkali metal; 0% to about 5% by weight of a dispersant; and 0 wt % to about 5 wt % viscosity modifier.

13. The method according to any one of claims 8 to 11, further comprising: casting a solvent-containing ceramic green body from the precursor mixture, wherein the casting is performed in a casting chamber comprising a casting vapor pressure of about 100 Pascals or more of the solvent in the solvent-containing ceramic green body; transporting the solvent-containing ceramic green body from a casting chamber to a solvent loading chamber comprising a solvent in the solvent loading chamber having a chamber vapor pressure of about 20 Pascals or greater and a casting vapor pressure greater than or equal to the casting vapor pressure; heating the ceramic green body containing the solvent at a chamber temperature of a solvent loading chamber of about 40° C. or higher, the chamber temperature of the solvent loading chamber being greater than the temperature of the casting chamber; transporting the ceramic green body containing a solvent from a solvent loading chamber to a drying chamber having a chamber vapor pressure greater than a drying vapor pressure of the solvent in the drying chamber; and The solvent-containing ceramic green body is heated at a drying temperature of a drying chamber to form a solvent-free ceramic green body corresponding to the ceramic green body, the drying temperature being greater than the chamber temperature.

14. The method of claim 13, wherein: The casting vapor pressure is maintained by a solvent reservoir of solvent in fluid communication with the casting chamber, the solvent reservoir being heated at a reservoir temperature greater than the casting temperature of the casting chamber.

15. The method according to any one of claims 13 to 14, wherein: The casting vapor pressure is about 1000 Pascals to about 50000 Pascals.

16. The method according to any one of claims 13 to 15, wherein: The solvent-containing ceramic green body is heated at the chamber temperature of the solvent loading chamber for about 3 minutes to about 10 minutes.

17. The method of any one of claims 13-16, further comprising introducing atmosphere into the drying chamber from a substantially solvent-free environment at least at a distal end and removing atmosphere from the drying chamber at an interface between the solvent-loaded chamber and the drying chamber at a proximal end, and the proximal end is opposite to the distal end.

18. The method of claim 17, wherein: The average velocity of the atmosphere above the solvent-containing ceramic green body in the drying chamber is from about 0.01 meters per second to about 0.1 meters per second.

19. The method according to any one of claims 17 to 18, wherein: Atmosphere introduction occurs at the distal end and at least one additional location between the distal end and the proximal end.

20. The method according to any one of claims 13 to 19, wherein: Solvents include: Propylene glycol, methyl ethyl ketone, dimethyl carbonate, toluene, or a combination thereof.

21. A solvent annealing apparatus comprising: a casting chamber comprising a casting apparatus configured to form a solvent-containing ceramic green body from the precursor mixture, the casting chamber being in fluid communication with the solvent reservoir; a solvent loading chamber comprising at least one heating device configured to maintain a temperature of the solvent loading chamber; and a drying chamber comprising a ventilation system configured to circulate an atmosphere from a substantially solvent-free environment through the drying chamber, The solvent loading chamber is located between the casting chamber and the drying chamber, and is separated from the drying chamber by a baffle.

22. The solvent annealing apparatus of claim 21, wherein: The casting vapor pressure of the solvent in the solvent-containing ceramic green body in the casting chamber is configured to be greater than or equal to the chamber vapor pressure of the solvent in the solvent-loading chamber, and the chamber vapor pressure is configured to be greater than the drying vapor pressure of the solvent in the drying chamber.

23. The solvent annealing apparatus according to any one of claims 21 to 22, wherein: The ventilation system is configured to introduce atmosphere from a substantially solvent-free environment at least at a distal end of the drying chamber opposite the proximal end of the drying chamber having baffles, and the ventilation system is configured to remove atmosphere from the drying chamber at the proximal end of the drying chamber.

24. The solvent annealing apparatus of claim 23, wherein: The drying chamber includes a plurality of orifices including a first orifice at a distal end of the drying chamber and at least one additional orifice between the distal end and the proximal end, the first orifice and the at least one additional orifice configured to introduce an atmosphere from a substantially solvent-free environment.